Preparation of MXene/MnO2/wood photothermal evaporator for efficient solar-driven water purification - Nan Zheng; Atian Xie; Guojun Cheng; Quan Li; Zhaozhao Li; Jiuyun Cui (Desalination, 2026)

Late Miocene pollen record and quantitative paleoclimate and paleoelevation reconstructions for the Jianzha Basin, northeastern Tibetan Plateau - Beibei Zhang; Chaofeng Fu; Feng Wang; Fengyan Lu; Chen Liang; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Constraints of zircon and apatite on crystal accumulation and melt extraction during the formation of the Late Triassic Dulan volcanic-intrusive complex, East Kunlun Orogenic Belt, Western China - Kai-Pei Lu; Yu-Fang Zhong; Chang-Qian Ma; Gui-Zhi Huang; Huai Xiong; Si-Yu Yang; Quan-Cheng Lian (Journal of Asian Earth Sciences, 2026)

Process intensification of dilute methane abatement via a novel bidirectional tidal biofilter: Performance and mass-transfer mechanism - Heng Xu; Siyuan Shang; Quan Yuan; Zhiqiang Zuo; Jianbin Wang; Min Zheng; Zhenkang Wu; Xi Cheng; Huijiao Wang; Qi Qiu; Xinyu Zhang; Dawn E. Holmes (Chemical Engineering Journal, 2026)

Molten salt assisted thermochemical conversion of waste for production of sustainable fuels and chemicals: A review - Rehman Farooq; Cui Quan; Xizhi Cheng; Ye Shui Zhang; Aneta Magdziarz; Ningbo Gao (Biomass and Bioenergy, 2026)

Integrated network pharmacology and experimental validation to elucidate the mechanism of WIN55,212–2 in mitigating sepsis-induced pulmonary fibrosis in mice - Quan He; Dei-xing Yang; Lin Duo; Tong-ling Shi; Yuan-wei Yang; Jie-cheng Li; Shu-ting Li; Shang-shang Zhu (Tissue and Cell, 2026)

Paleogene vegetation dynamics in low-latitude Asia: spatio-temporal evolution of the Guangxi biodiversity hotspot - Caihong Yin; Chengyu Song; Lian Zhang; Qijia Li; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Boosting lattice oxygen activation and active sites generation via an Mn-O electron bridge for efficient simultaneous oxidation of toluene and NO over Mn5Co4Ce3Ox catalyst - Lei Gao; Yukai Quan; Ping Fang; Dong Xie; Caiting Li; Cheng Sun; Jiahao Zhang; Ruotao Bai; Jingshuo Zhang (Fuel, 2026)

Enhancing the inhibitory effect of epigallocatechin gallate on formation of heterocyclic amines via protein complexation - Xiulan Dang; Xiaoting Hu; Yan Yan; Wei Quan; Xufeng Wang; Yunhui Cheng; Ye Jiao (Food Chemistry, 2026)

Low relative humidity in dust event weakens SO2 conversion - Yubing Pan; Jiannong Quan; Pengkun Ma; Qianqian Wang; Zhigang Cheng; Yinan Wang (Atmospheric Environment, 2026)

Directivity effect of ground motions of the 2024 Mw7.4 Hualien Earthquake in Taiwan, China - Liang Qian; Jin-Cheng Li; Qiang Ma; Quan-Cai Xie; Xiao-Nan Zhang; Si-Han Yu (Applied Geophysics, 2026)

Characteristics and potential formation mechanisms of dissolved organic matter at the water-sediment interface and assessment of its release potential in the eastern pacific polymetallic nodule area - Yuanhao Zhang; Zhidan Liu; Li Zou; Cheng Wu; Xueqing Zhang; Haibing Ding; Yongzheng Quan; Yonggang Jia (Water Research, 2026)

Tracking the first arrival in Asia: Early Eocene Thuja (Cupressaceae) from Lingbao, Henan, central China - Wei Wang; Qijia Li; Hui Jia; Congyi Wu; Cheng Quan (Review of Palaeobotany and Palynology, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Impact of anions on the assembly of layer-by-layer nanofiltration membranes for ion separation - Mengxiang Cheng; Quan Yuan; Yangshuo Xu; Yue-Biao Zhang; Tao He (Desalination, 2026)

Porous solar evaporator with hierarchical photothermal structure for highly-performance desalination and water remediation - Yuqian He; Chunguang Liu; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Xi Quan Cheng (Chemical Engineering Journal, 2026)

Early Fibroblast Remodeling Associated with Lung Tissue Preservation After FLASH Irradiation - Caihui Li; Luhao Tan; Qixiang Liu; Zhihui Li; Menghua Li; Xuefeng Yang; Guofu Dong; Cheng Quan; Jie Ping; Changzhen Wang; Hao Lu (Phenomics, 2026)

Ecological stability of the Late Miocene Tatsumi-toge biota revealed by plant–insect interactions - Cui Wang; Atsushi Yabe; Bingshan Niu; Wei Wang; Qijia Li; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Neonicotinoid insecticides induced neurotoxicity in SH-SY5Y cells via oxidative stress and mitochondrial dysfunction - Ziyan Cheng; Xinru Wang; Zhimin Yang; Jingtong Yu; Nan Zhao; Chenyang Ji; Quan Zhang; Meirong Zhao (Journal of Hazardous Materials, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Nuclear receptor co-activator 4 interacts with RUVBL1/2 to maintain genome integrity through double-strand break repair - Yingying Chen; Qi Zhang; Zongjian Tao; Shaoting Lv; Cheng Quan; Gangqiao Zhou; Hongxia Chen (DNA Repair, 2026)

Correction to “Choline chloride enables low-severity NaOH/Triton-X 100 pretreatment and lignin upgrading to enriched aromatic bio-oil and porous biochar” [Chem. Eng. J. 2026;538:176853. https://doi.org/10.1016/j.cej.2026.176853] - S. Al Azad; E. Kargaran; M. Saleknezhad; Y. Cheng; C. Quan; J. Chen; C. Sun; M. Madadi; F. Sun (Chemical Engineering Journal, 2026)

Reassessing the Neolithic chronology and cultural development at the Dadiwan Site - Zhiqi Pei; Jian Wang; Yuanxin Li; Changchun Liu; Yongbo Quan; Haiming Li; Yishi Yang; Ting Cheng; Mingjie Yi; Le Zhang; Hui Wang; Huan Xia; et al. (Science China Earth Sciences, 2026)

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Phosphate-buffered saline as pH regulators for citrus postharvest handling water, maintain fruit quality by enhancing the phenylpropanoid metabolic pathway - Yanfei Zhu; Huan Liu; Yunxi Xiao; Zhiqiang Xiong; Ling Shen; Jiajun Tang; Zhifeng Zhu; Linlin Zhong; Rangwei Xu; Quan Sun; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Synergistic effects between Si, Cu and K promoters and their influences on the structures and performances of Fe-based Fischer–Tropsch synthesis catalysts - Xiaoming Suo; Zhengjia Li; Jie Cen; Meng Cheng; Quan Lin; Zhuowu Men; Weizhen Li; Nan Yao; Xiaonian Li (Fuel, 2026)

Dynamic and residual static performance of steel beam-column subframes with extended end-plate connections under elevated temperatures - Kai Qian; Quan Luo; Zhi Li; Xi Lan; De-Cheng Feng (Engineering Structures, 2026)

The spatial rainfall pattern in China during the 4.2 ka event and its forcing mechanism - Bin Zhao; Chuntong He; Jiangying Wu; Yongjin Wang; Kan Zhao; Quan Wang; Hai Cheng; Yijia Liang (Climate Dynamics, 2026)

Performance study of nickel-potassium/calcium oxide catalyst for carbon dioxide capture and conversion - Cui Quan; Haojie Suo; Xiaobin Liu; Xizhi Cheng; Ningbo Gao (Sustainable Chemistry and Pharmacy, 2026)

Building soil organic matter differing in physical fractions for fertilizer nitrogen retention - Quan Tang; Qingde Li; Xiaozhi Wang; Yuanyuan Huang; Tim J. Daniell; Enxuan Wu; Jing Wang; Feiyi Zhang; Zhenwang Li; Scott X. Chang; Zucong Cai; Yves Uwiragiye; et al. (Soil Biology and Biochemistry, 2026)

Evolutionary and phytogeographic insights into Zanthoxylum (Rutaceae) fossil seeds in South China from the Oligocene to Pleistocene - Shenglan Xu; Yuan Zheng; Hanzhang Song; Luliang Huang; Xiaoyan Liu; Cheng Quan; Jianhua Jin; Xinkai Wu (Review of Palaeobotany and Palynology, 2026)

Early Eocene Platanus from central China confirmed by geometric morphometrics and its implications for palaeoclimate and palaeobiogeography - Hui Jia; Tian-Ze Zhu; Jian Pan; Tian-Qi Dong; Tian-Xiao Zhang; Cheng Quan (Palaeoworld, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Health risk assessment of metal(loid)s in the topsoils of an operating industrial park based on bioaccessibility and quantitative source apportionment - Yiwei Gong; Kaiming Yang; Weici Quan; Jiawen Zhang; Yuxi Wu; Rui Wang; Yadi Ai; Kai Yang; Hongguang Cheng (Journal of Environmental Sciences, 2026)

High energy density and power density foam nickel-loaded 3D chromium-doped carbon nanosheet supercapacitor electrodes - Jianglong Cheng; Yaru Li; Baosen Mi; Quan Wang; Hongbin Wang; Tao Zhou; Haipeng Hou; Yumeng Zhu (Fuel, 2026)

A gas-permeable edible coating alleviates CO2-induced off-flavor formation and reduces weight loss in postharvest citrus fruit - Lili Lu; Qujuan Luo; Zhen Huang; Weijie Liu; Yunqian Zou; Yanqing Yang; Rangwei Xu; Shilin Liu; Feng Zhu; Quan Sun; Zhifeng Zhu; Yunjiang Cheng (Food Chemistry, 2026)

Choline chloride enables low-severity NaOH/Triton-X 100 pretreatment and lignin upgrading to enriched aromatic bio-oil and porous biochar - Salauddin Al Azad; Ehsan Kargaran; Maryam Saleknezhad; Yuanchao Cheng; Conghui Quan; Junyao Chen; Chihe Sun; Meysam Madadi; Fubao Sun (Chemical Engineering Journal, 2026)

Tracing the evolution of granitic magmas revealed by fayalite–ferrosilite-bearing microgranular enclaves in Jiuyishan area of South China Block - Jing-Yi Liu; Quan Ou; Jian-Qing Lai; Feng Zi; Kun Wang; Wen-Zhou Xiao; Zhi-Cheng Lin; Cui-Yun Wang; Qian-Cheng Feng; Jia Liao (Acta Geochimica, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Cold exposure impairs the muscle growth-promoting effect of nighttime-restricted feeding by desynchronizing mitochondrial energy supply rhythm in rabbits - Yuan-Yuan Tan; Xiao-Han Ma; Chun-Hua Shan; Shuai He; Quan-Gang Wang; Meng-Qi Zhu; Jian-Xiang Cheng; Ke-Hao Zhang; Lei Zhang; Zhong-Ying Liu; Yao Guo; Zhong-Hong Wu (Journal of Thermal Biology, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Phosphorus role in bioconversions of food waste by black soldier fly larvae - Yu Wang; Jiawei Quan; Mengyao Li; Bo Liu; Xiang Cheng; Yan Sun; Zengwei Yuan (Waste Management, 2026)

Seneca Valley virus 2B and 3 C proteins attenuate the cGAS-STING signaling pathway by targeting STING for degradation - Xuexia Wen; Meijun Zhou; Shijie Xie; Jin Yuan; Yu Hong; Ruiyi Ma; Liwei Zhao; Dan Wang; Rong Quan; Peipei Cheng; Jiangwei Song (Veterinary Microbiology, 2026)

Corrigendum to “Utilization of current pyrolysis technology to convert biomass and manure waste into biochar for soil remediation: A review” [Sci. Total Environ., 864 (2023), 160990] - Shimeng Tan; Guoying Zhou; Quan Yang; Shengbo Ge; Junang Liu; Yoke Wang Cheng; Peter Nai Yuh Yek; Wan Adibah Wan Mahari; Sieng Huat Kong; Jo-Shu Chang; Christian Sonne; William Woei Fong Chong; et al. (Science of The Total Environment, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Investigation on thermal runaway mechanism of tert-butyl peroxy benzoate using calorimetry analysis coupled with free radical spin-trapping technology - Zhi-Ping Li; Xiao-Yu Fang; Jun-Cheng Jiang; Lei Ni; Zhi-Quan Chen; Yuan-Yuan Wang (Journal of Environmental Chemical Engineering, 2026)

Effects of baking degree of Longjing green tea on flavor attributes, antioxidant activity and advanced glycation end products - Ran Wei; Xiao-Yu Zhong; Kayama Kayama; Yu-Hong Lin; Fang-Ting Qin; Zhu-Cheng Su; Yong-Quan Xu (Food Research International, 2026)

Fabrication of acid-resistant nanofiltration membranes with intrinsic positive charges for lithium recovery - Yue Shen; Bingxin Gu; Xinhe Zhang; Yu Guo; Huiting Zhang; Cheng-Gang Jin; Bohao Chen; Yahua Lu; Gangqiang Yu; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Oceanic deoxygenation linked to enhanced water column stratification in the eastern Tethys during Cretaceous Oceanic Anoxic Event 2 - Yu Liang; Yong-Xiang Li; Hongxuan Lu; Huanye Wang; Cece Wang; Cheng Quan; Weiguo Liu; Mei-Fu Zhou; Zhonghui Liu (Global and Planetary Change, 2026)

Depolymerization mechanism of α-O-4 type lignin in pyrolysis through a cyclohexadienone intermediate - Jiaxue Zhu; Quan Tang; Xun Gong; Erwei Leng; Yuanwang Deng; Hong Tian; Shan Cheng; Jiaqiang E (Fuel, 2026)

Decoupling Zn2+/H+ co-insertion in VOMoO4/rGO heterostructure for dendrite-free symmetric zinc-ion batteries - Yexin Luo; Quan Kuang; Yunbo Li; Jianxin Zhan; Yunhua Cheng; Qinghua Fan; Youzhong Dong; Yanming Zhao (Chemical Engineering Journal, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Ecological roles of lactic acid bacteria biodiversity and cross-feeding in shaping the flavor landscape of traditional Huangjiu fermentation - Chao-Jie Zhu; Yi-Ling Zhong; Yong-Zhu Zhang; Zhi-Chu Shan; Hong-Yan Qu; Fei Cheng; Wei Feng; Peng Wang; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Bioresource Technology, 2026)

Floral fragrance in sweet osmanthus majorly repels pollen feeders - Hui-Hui Feng; Cheng-Xi Tan; Shao-Cheng Huang; Shuang-Quan Huang (Science China Life Sciences, 2026)

Corrigendum to “Cattle manure hydrochar posed a higher efficiency in elevating tomato productivity and decreasing greenhouse gas emissions than plant straw hydrochar in a coastal soil” [Sci. Total Environ. 912 (2024), 168749] - Xiao Wang; Qingxian Kong; Yadong Cheng; Hao Zheng; Xueyang Yu; Yue Quan; Xiangwei You; Yiqiang Li (Science of The Total Environment, 2026)

Study on PAH and soot formation in 2,5-dimethylfuran counterflow diffusion flames with ammonia addition - Yishu Xu; Jiahui Wu; Ronghao Yu; Bowen Wang; Yanhong Quan; Hanxiao Liu; Kai Zhang; Xiaobei Cheng (Fuel, 2026)

Gram-scale synthesis of ultra-small naked melanin nanoparticles with high aqueous solubility for theranostic applications in vivo - Xingyu Gao; Ruihan Liu; Yao Li; Ran Cheng; Ruxia Liu; Jiaojiao Yu; Xuejun Zhang; Shao-Kai Sun; Quan Zou (Chemical Engineering Journal, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Ilex subg. Prinos (Aquifoliaceae) from the upper Miocene of Beihai, low-latitude China: New insights for phylogeny - Bingshan Niu; Qijia Li; Hui Jia; Jianhua Jin; Cheng Quan (Review of Palaeobotany and Palynology, 2026)

The Asian summer monsoon evolution from the late Younger Dryas to the early Holocene - Bin Zhao; Chuntong He; Kan Zhao; Yongjin Wang; Jiangying Wu; Quan Wang; Hai Cheng; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Towards more accurate estimation of methane emissions from urban lakes: Unraveling the impact of diel variation - Yadi Ai; Hongguang Cheng; Kaiming Yang; Yiwei Gong; Weici Quan; Yuxi Wu; Jiawen Zhang; Di Huang (Journal of Hydrology, 2026)

Effect of freeze-thaw cycles on nitrogen retention in an alpine topsoil amended with peanut shell hydrochar - Yuxi Wu; Jiawen Zhang; Yadi Ai; Weici Quan; Yiwei Gong; Kaiming Yang; Jin Gao; Lu Li; Caiwei Hao; Wenbo Li; Wenjie Ai; Kai Yang; et al. (Environmental Research, 2026)

Water table-driven divergent patterns and drivers of particulate and mineral-associated organic carbon in alpine peatlands - Han Zheng; Mengjie Liu; Houkun Chu; Paul P.J. Gaffney; Junxiao Pan; Quan-Cheng Wang; Yang Li; Dashuan Tian; Ruiyang Zhang; Ronglei Zhou; Ning Liu; Fei Wu; et al. (CATENA, 2026)

Sucrose induces simultaneous autolysis attenuation and keratinase production enhancement in Bacillus subtilis WB600 - Yi-Ning He; Dao-Quan Jiao; Ge-Ge Chen; Xiao-Dong Pei; Zhi-Qiang Zhou; Fan Li; Yu-Hui Fang; Cheng-Hua Wang (Bioresource Technology, 2026)

Soil microplastics pollution can reduce viral abundance and have less consistent impacts on bacteria - Wen-Wen Huang; Yanan Cheng; Dong-Hao Zhou; Quan-Guo Zhang; Hao Yu (Applied Soil Ecology, 2026)

Calophyllum (Calophyllaceae) with high leaf mass per area from the upper Miocene of Beihai, low-latitude China - Shu-Ran Tang; Qi-Jia Li; Hui Jia; Jian-Hua Jin; Cheng Quan (Palaeoworld, 2025)

Greenland supraglacial lakes albedo-depth parameterization from multi-source remote sensing: An application of lake-albedo feedback modeling - Jiake Wu; Lei Zheng; Zhuoqi Chen; Quan Zhou; Chuyue Peng; Qi Liang; Teng Li; Baojuan Huai; Weijun Sun; Xiao Cheng; Robert Law; Fengming Hui (Journal of Hydrology, 2025)

Enhancing anaerobic methane production from corn straw: Promoting lignocellulosic biomass biodegradation via aeration in liquid fraction of digestate for green and efficient pretreatment - Bi-Long Chen; Ting-Ting Zhang; Aqsa Arooj; Cheng Xu; Jia-Cheng E. Yang; Mika Sillanpää; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

Fabrication of Rubus chingii Hu ellagitannins-loaded W/O/W double emulsion gels stabilized by WPI/pectin complexes: Physicochemical properties, digestion characteristics, and transformation of ellagitannins - Dong-Jun Hou; Quan-yuan Xie; Ming-Shun Chen; Yu-Lin Cheng; Bing Zhang; Zong-cai Tu; Lu Zhang (Food Chemistry, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Sodium promotion in hydrothermal carbon-derived Fe/Fe₃C catalysts enables reversal of olefin-paraffin selectivity in Fischer-Tropsch synthesis - Mingqiang Chen; Xuemei Shen; Chang Li; Yishuang Wang; Defang Liang; Quan Wang; Chunyue Cheng; Chuannan Nie; Jiawen Hu (Chemical Engineering Journal, 2025)

Corrigendum to ‘Apatite and Zircon as key indicators for effusive-explosive transition in the Leningcou Volcano: Middle Triassic Volcanic activity in the East Kunlun Orogenic Belt’ [Chemical Geology 678 (2025) 122670] - Gui-Zhi Huang; Chang-Qian Ma; Bin Liu; Zhen-Hua Xue; Huai Xiong; Kai-Pei Lu; Quan-Cheng Lian; Ke Gao; Meng-Yu Zhang; Si-Yu Yang (Chemical Geology, 2025)

Machine learning coupling microbial succession to decipher gas stripping-reinforced sulfate reduction for hydrogen sulfide removal - Ting-Ting Zhang; Ei Myat Mon Oo; Bi-Long Chen; Lin Liu; Quan-Bao Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Bioresource Technology, 2025)

FTO-mediated Nrf2 demethylation alleviates high glucose-induced oxidative stress and apoptosis in retinal pigment epithelial cells - Quan Cheng; Liqiong Zhou; Xinyu Fan; Minjun Ma; Chunhui Zhang; Xu Zha; Yuanping Zhang (Molecular Biology Reports, 2025)

Elastic–Viscoplastic Modeling and FLAC3D Implementation for Long-Term Settlement of Immersed Tunnels under K0 Consolidation - Hongkang Zhu; Lei Kou; Quan Cheng; Jingyang Li; Jingxi Zhang (Geotechnical and Geological Engineering, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Rapid and efficient stem segment regeneration propagation system for Euonymus bungeanus - Kai-Ge Cui; Hao-Lin Wang; Wen-Yue Quan; Zhuo-Zhuo Ye; Cheng-Ri Zhao (South African Journal of Botany, 2025)

Ensemble atomic sites for acidic oxygen evolution: mechanisms, atomic engineering, and AI-assisted screening - Wenjia Qu; Xingen Lin; Handuo Zheng; Jianuo Liu; Cheng Qian; Kong Chen; Huang Zhou; Yafei Zhao; Quan-Hong Yang; Yuen Wu (Science Bulletin, 2025)

Chinese speleothem evidence of the early-mid Holocene transition and the instability of Asian summer monsoon - Bin Zhao; Yongjin Wang; Kan Zhao; Jianjun Yin; Quan Wang; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Global and Planetary Change, 2025)

Black phosphorus integrated self-assembled silk fibroin nanofibrous microspheres: Micro-hotbeds for accelerating bone regeneration - Jiangfeng Cai; Qichao Cheng; Chi Yan; Suting Zhong; Fang Lei; Yajun Shuai; Jie Wang; Zongpu Xu; Quan Wan; Chuanbin Mao; Mingying Yang (Chemical Engineering Journal, 2025)

Late Pleistocene megalake system in the Yinchuan-Hetao rifting basins, upper reaches of the Yellow River - Xiaobo Liu; Cheng Quan; Zhonghui Liu; Rongxi Li (Quaternary Science Reviews, 2025)

Fossil involucres and a nutlet of Ostrya (Betulaceae) from the upper Eocene of Shaanxi and their biogeographic implications - Jiao Huang; Hui Jia; Rui-Feng Yan; Xiang-Ning Meng; Zhuo-Chen Han; Tian-Qi Dong; Jian Pan; Cheng Quan (Palaeoworld, 2025)

Partitioning, renal clearance, and internal exposure assessment of liquid crystal monomers (LCMs): Based on paired serum and urine of general population in Northwest China - Kaiming Yang; Yiwei Gong; Guanlan Wu; Jiawen Zhang; Weici Quan; Yuxi Wu; Yadi Ai; Di Huang; Kai Yang; Hongguang Cheng; Qingrui Zhang; How Yong Ng (Journal of Hazardous Materials, 2025)

Nacre-inspired carbon-based thermal conductive networks for thermal management in phase change energy storage - Xiang Chen; Yuefeng Zhang; Biao Cheng; Huafeng Quan; Dong Huang; Chong Ye; Jinshui Liu (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Estimating evapotranspiration from deciduous broadleaf forests by considering the effect of foliar litter - Chenhao Fu; Shujing Qin; Lei Cheng; Lingcheng Li; Quan Zhang; Xuxin Lei; Pan Liu; Lu Zhang (Agricultural and Forest Meteorology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Vertical mixing of pollutants and secondary inorganic aerosol formations over Beijing, China - Jiannong Quan; Pengkun Ma; Yubing Pan; Siyu Cheng; Qianqian Wang; Linhui Lan; Lindong Dai; Yuzheng Wang; Yongchun Liu (Atmospheric Environment, 2025)

Genome-wide identification of the SAM-dependent methyltransferase members and functional analysis of GmSAMMt30 in soybean (Glycine max) under salt-alkali stress - Wenjing Zhang; Jinqi Yu; Zitian He; Jiaxuan Guo; Changchao Huang; Qingqing Xu; Xianya Dong; Ziyi Yang; Beixi Chen; Cheng Quan; Meiqing Li; Qi Zhang; et al. (Theoretical and Applied Genetics, 2025)

Construction of an urban collaborative emergency response network based on a disaster chain: an example of typhoon disaster in Fujian Province - Boyi Fu; Xinyue Liang; Xin Wen; Shuangbao Zhang; Quan Cheng (Natural Hazards, 2025)

Two new cadinane-type sesquiterpene glycosides from Dendrobium findleyanum - Zi-Xi Lin; Zhong-Quan Cheng; Dan Yang (Natural Product Research, 2025)

Response of black tea powder and its fermentation products on growth performance, antioxidant capacity, and gut microbiota of Cherax quadricarinatus - Xian-Jing Zhang; Jiao-Fen Lin; Cheng-Jian Wu; Jie-Quan Xie; You-Shu Cai; Xu-Yin Lin (Frontiers in Marine Science, 2025)
Introduction The overuse of antibiotics in aquaculture has raised concerns, necessitating the exploration of sustainable alternatives. This study evaluated tea-derived additives as potential substitutes. Methods This study evaluated the effects of black tea powder (BTP) and black tea powder-probiotics mixed fermentation product (TPMFP) on Cherax quadricarinatus growth, antioxidant capacity, and gut microbiota. Cherax quadricarinatus were fed diets supplemented with BTP (1–6%) or TPMFP (2%) for 84 days. Results The addition of BTP (<2%) to the feed enhances the weight, carapace length, and muscle protein content of Cherax quadricarinatus , while higher doses (>3%) showed adverse effects. Moreover, the addition of BTP (1%-6%) can significantly reduce the muscle content of CHO, TG, and HDL (P<0.05). The TPMFP group exhibited the highest muscle protein content and significantly elevated hepatopancreatic SOD, GSH-PX, and AKP activities (P < 0.05), indicating improved antioxidant capacity. Gut microbiota analysis revealed dose-dependent shifts, with Proteobacteria dominating (>70%) and Aeromonas increasing with BTP levels. TPMFP significantly increased the α-diversity indices (richness and evenness) of the gut microbiota. The Mantel test confirmed the relationship between the antioxidant function of the microbial community, with Proteobacteria positively correlated with GSH-PX/SOD, while Fusobacteria and Tensionella negatively correlated with antioxidant enzyme activity. Discussion This study provides a foundation for using tea-derived additives as a sustainable alternative to antibiotics in aquaculture.In the future, metagenomic analysis of key metabolic pathways can be combined to optimize the mechanistic explanation of the application and efficacy of BTP and TPMFP.

A mechanistic study of the efficient adsorption for platinum(IV) by amino-functionalized calix[4]arene - Tao Ge; Quan Shi; Liang Xu; Yifan Yang; Mengyang Li; Cheng Yang; Yongpan Tian; Zhuo Zhao (Science of The Total Environment, 2025)

Explosibility and thermal hazards of unpremixed H2/Mg dust layer in the confined space - Rong Liu; Yang-Fan Cheng; Quan Wang; Xu-Guang Wang (Process Safety and Environmental Protection, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Corrigendum to “In-situ grown cauliflower-like CuSn zinc anodes with permselective PEDOT: PSS coating for synergistic construction of long-cycle dendrite-free zinc ion batteries” [Chem. Eng. J. 508 (2025) 161005] - Yanjing Rong; Junwen Duan; Quan Kuang; Zhixiong Xu; Yunbo Li; Jianguo Li; Qinghua Fan; Youzhong Dong; Yanming Zhao; Yunhua Cheng (Chemical Engineering Journal, 2025)

Minor dibenzocyclooctadiene lignans with antifibrotic potential from the fruits of Schisandra chinensis - Ping Sun; Quan-Hao Wei; Xin-Cheng Zhuang; Hua Zhang (Phytochemistry, 2025)

Recovery and regeneration of ternary cathode materials through Solid-State reactions - Tiantian Lin; Ketai Ren; Honglai Liu; Quan Li; Cheng Lian; Jingkun Li (Chemical Engineering Journal, 2025)

Metabolite changes of mung bean milk analogue following germination and/or fermentation with probiotic Limosilactobacillus reuteri - Ricco Tindjau; Yi-Cheng Ler; Ying Luo; Shao-Quan Liu (Biocatalysis and Agricultural Biotechnology, 2025)

Highly selective electrochemical sensing of hydroquinone and catechol using Co nanoparticles anchored on N-doped carbon nanotube hollow sphere - Xiaomin Cheng; Xiaojuan Shui; Quan Yang; Huimin Ma; Yuanyuan Zhang; Ting Zeng; Juan Yang; Zhen Wu; Xiuhua Zhang; Nianjun Yang (Analytica Chimica Acta, 2025)

Corrigendum to “Early Oligocene Asian monsoon: Evidence from the Fuping flora of Baise, Guangxi, low-latitude China” [Palaeogeography, Palaeoclimatology, Palaeoecology, Volume 662, 15 March 2025, 112783] - Qiaoyi Ma; Yusheng (Chris) Liu; Qijia Li; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Early Eocene Metasequoia and Taxodium (Cupressaceae) from Lingbao, Henan Province and their implication for a perhumid climate in central China - Ping Liu; Hui Jia; Li Xu; Yu Li; Ming-Yue Luo; Tian-Qi Dong; Jiao Huang; Cheng Quan (Palaeoworld, 2025)

Nanoconfinement photothermal effect in metal-organic framework for enhanced peroxymonosulfate activation - Cheng-Min Wang; Zhao-Quan Wen; Dong-En Zhang; Xin-Xin Lu; Tao An; Yu-Hui Luo (Journal of Environmental Chemical Engineering, 2025)

Fate of myofibrillar protein-bound Nε-(carboxymethyl)lysine in the presence of the human colonic microbiota after gastrointestinal digestion - Shuqi Hao; Zeyu Lu; Mengyu Ye; Na Li; Jiayi Hu; Wei Quan; Jiwen Cheng; Huaide Xu; Mei Li (Food Bioscience, 2025)

Synthesis and biological evaluation of sulfonamide derivatives containing imidazole moiety as ALK5 inhibitors - Shu-Yan Ding; Yu-Xuan Yang; Chuang Liu; Xu-Yin Quan; Zi-Han Zhao; Cheng-Hua Jin (Molecular Diversity, 2025)

RBM15 promotes m6A methylation and stability of KLF6 mRNA to accelerate pyroptosis of retinal ganglion cells in early-stage diabetic retinopathy - Liqiong Zhou; Chunhui Zhang; Quan Cheng; Minjun Ma; Xinyu Fan; Yuanhui Han; Xu Zha; Yuanping Zhang (Journal of Molecular Histology, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Electronic-ionic dual-conductive framework/channel stabilized Zn anodes for high-performance aqueous Zn-ion batteries - Qian He; Zekai Zhang; Hongchun Mu; Cheng Lian; Quan Li; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Research on magnetron sputtering thin films as electrode materials for supercapacitors - Jianglong Cheng; Baosen Mi; Quan Wang; Hongbin Wang; Tao Zhou; Yaru Li; Haipeng Hou; Yumeng Zhu (Chemical Engineering Journal, 2025)

Apatite and Zircon as key indicators for effusive-explosive transition in the Leningcou Volcano: Middle Triassic Volcanic activity in the East Kunlun Orogenic Belt - Gui-Zhi Huang; Chang-Qian Ma; Bin Liu; Zhen-Hua Xue; Huai Xiong; Kai-Pei Lu; Quan-Cheng Lian; Ke Gao; Meng-Yu Zhang; Si-Yu Yang (Chemical Geology, 2025)

Morphological diversity of the sensilla of the larval mouthparts among three species of Corydalidae (Insecta, Megaloptera) with reference to their possible functions - Yu Tong Li; Yu Meng Dai; Cheng Quan Cao (Zoomorphology, 2025)

Sensitivity and regulation factors of soil organic carbon content in steppe and desert—steppe grasslands of the Mongolian Plateau - Zhijia Quan; Yunxiang Cheng; Mitsuru Tsubo; Masato Shinoda (Plant and Soil, 2025)

Construction of a Controlled Drug Delivery and Optical Monitoring System for Colorectal Cancer via Natural Fiber Modification - Quan Cheng; Huazhou Fu; Yong Mao (Journal of Medical and Biological Engineering, 2025)

PLAGL2-STAU1-NCOA4 axis enhances gastric cancer peritoneal metastasis by resisting ferroptosis via ferritinophagy - Shansong Huang; Peicheng Ji; Peng Xu; Kanghui Liu; Han Ge; Zhengyuan Yan; Quan Cheng; Jialun Lv; Diancai Zhang (Apoptosis, 2025)

A text feature extraction model for hazardous chemical recovery identification and attribute classification embedded in domain knowledge graph - Quan Cheng; Shuangbao Zhang; Lanyu Yang (Environmental Monitoring and Assessment, 2025)

Molecular composition difference of electron donating moieties between natural organic matter and effluent organic matter probed by chlorine dioxide - Quan Gao; Yanheng Pan; Yangjian Zhou; Jianglin Peng; Qingqing Kong; Yanhui Cheng; Qing-Long Fu; Xin Yang (Water Research, 2025)

Coupled iron oxides and microbial-mediated soil organic carbon stabilization across tea plantation chronosequences - Quan Tang; Wei Li; Jing Wang; Feiyi Zhang; Wenxia Dai; Zhenwang Li; Shengsen Wang; Weiqin Yin; Yi Cheng; Xiaozhi Wang (Soil and Tillage Research, 2025)

Early Oligocene Asian monsoon: Evidence from the Fuping flora of Baise, Guangxi, low-latitude China - Qiaoyi Ma; Yusheng (Chris) Liu; Qijia Li; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Autophagy-mediated energy charge sustainability alleviated postharvest quality deterioration of strawberry (Fragaria × ananassa) - Yicheng Ren; Quan Ma; Dong Li; Yanpei Chen; Qinyang Cheng; Zisheng Luo (Food Chemistry, 2025)

Concurrent optimization of truss structures and build directions for multi-axis additive manufacturing - Jun Ye; Xiaoyang Lin; Hongjia Lu; Linwei He; Guan Quan; Cheng Huang; Paul Shepherd (Engineering Structures, 2025)

Dysregulation of Serum Exosomal Lipid Metabolism in Schizophrenia: A Biomarker Perspective - Chen-Xi Xu; Wei Huang; Xiao-Jie Shi; Yang Du; Jia-Quan Liang; Xuan Fang; He-Yuan Chen; Yong Cheng (Molecular Neurobiology, 2025)

Deformation Characteristics and Stability Analysis of Soft-Hard Interbedded Tunnels - Mei-li Hu; Shun-chuan Wu; Shi-jiang Pu; Hai-yong Cheng; Ji-quan Ma (Geotechnical and Geological Engineering, 2025)

Precambrian tectonic evolution of the Songliao–Xilinhot block in the context of a supercontinent cycle: Evidence from Neoarchean granitoid rocks in the Longjiang area, NE China - Chao Zhang; Jingyu Quan; Zhenghong Liu; Cheng Qian; Chen Zhao; XinWei Wu; Jingsheng Chen; Yan Wang (Precambrian Research, 2025)

The diversity and disparity of mineral elements in global kiwifruits - Dawei LI; Yan Min; Chang Cheng; Xiaoying Liu; Xiaodong Xie; Gudeta Chalchisa; Cheng Peng; Quan Jiang; Naidong Xiao; Jianbo Cai; Caihong Zhong (Food Research International, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

The evolution of Fe5C2 with the carburization of N- and K-modified Fe/Fe3C core-shell catalysts during Fischer-Tropsch synthesis - Xuemei Shen; Chang Li; Yishuang Wang; Mingqiang Chen; Quan Wang; Defang Liang; Chunyue Cheng; Jun Wang (Chemical Engineering Journal, 2025)

CsbHLH6 positively regulates abscisic acid-mediated citrus fruit coloration during postharvest storage - Quan Sun; Zhengchen He; Yingzi Zhang; Di Feng; Ranran Wei; Lijun Chai; Wenwu Guo; Juan Xu; Yunjiang Cheng; Qiang Xu; Junli Ye; Xiuxin Deng (Postharvest Biology and Technology, 2025)

Binding mechanisms and phosphorus adsorption performance of soil mineral-BDOM complexes - Jinlong Yan; Xiangqian Zhou; Wei Zhang; Fengli Cheng; Hui Wang; Liqiang Cui; Guixiang Quan (Journal of Water Process Engineering, 2025)

Corrigendum to “Melatonin: A novel and beneficial substance in sweet potatoes through selenium application” [Food Chemistry 463 (2025), 141509/FOCH_141509] - Xianghan Cheng; Xuan Yang; Quan Zhang; Taiji Kou; WenBang Hou; Youjun Li (Food Chemistry, 2025)

Melatonin: A novel and beneficial substance in sweet potatoes through selenium application - Xianghan Cheng; Xuan Yang; Quan Zhang; Taiji Kou; WenBang Hou; Youjun Li (Food Chemistry, 2025)

Variation in microbial communities and network ecological clusters driven by soil organic carbon in an inshore saline soil amended with hydrochar in Yellow River Delta, China - Hui Yao; Yadong Cheng; Qingxian Kong; Xiao Wang; Ziguo Rong; Yue Quan; Xiangwei You; Hao Zheng; Yiqiang Li (Environmental Research, 2025)

Aromatic Chinese medicine-decorated mesoporous nanoenzyme overcomes multiple biological barriers for solid tumor treatment - Xiaolong Quan; Ben Hu; Yibing Li; Iman Zare; Fengyong Cheng; Huiqi Huang; Jun Liu; Peng Cao; Dan Zhou; Meng Yu (Chemical Engineering Journal, 2025)

A simply synthesized, silver ions-doped porous gold microparticles-based SERS aptamer sensor for ultrasensitive and broad-range quantitative detection of IL-6 - Bixia Liang; Zhixi Huang; Lingyan Cheng; Jin Quan; Zongxia Mou; Nan Li; Xin Cui (Analytica Chimica Acta, 2025)

pH threshold in controlling dominant nitrification pathway in acidic soils - Miaomiao Cao; Yong Li; Yuxuan Zhang; Debang Yu; Yves Uwiragiye; Jing Wang; Hang Jing; Quan Tang; Yinfei Qian; Ahmed S. Elrys; Yi Cheng; Zucong Cai; et al. (Agriculture, Ecosystems & Environment, 2025)

Fractionation and tidal characteristics of per- and polyfluoroalkyl substances in the estuarine maximum turbidity zone - Chang Liu; Xin-Xin Ma; Si-Quan Wang; Qin Li; Peng Cheng; Wei Hou; Yong-Yu Li; Wen-Long Li; Xin-Hong Wang (Science of The Total Environment, 2024)

Molecular characterization of oxidized organic nitrogen in the polluted urban atmosphere of Beijing - Lei Liu; Junying Sun; Xiaojing Shen; Xi Cheng; Qi Chen; Quan Liu; Yangmei Zhang; Jing Zheng; Wei Wen; Xin Ma (Science of The Total Environment, 2024)

Manganese(III) dominants the mobilization of phosphorus in reducing sediments: Evidence from Aha reservoir, Southwest China - Quan Chen; Jing-fu Wang; Meng-qiang Zhu; Hai-bo Qin; Peng Liao; Zhi-tong Lu; Peng-cheng Ju; Jing-an Chen (Science of The Total Environment, 2024)

Evaluation of phytohormone facilitation in microalgal biomass production using mathematical modeling - Zhuo-Xuan Wang; Zi-Ci Su; Guo-Quan Zhou; Yu Luo; Hui-Ran Chen; Zhuo Chen; Xuan Li; Cheng-Yue Liang; Guo-Hua Dao (Science of The Total Environment, 2024)

Middle to late Miocene cooling and drying in the northern Tibetan Plateau based on evidence from plant-insect interactions - Cui Wang; Yusheng (Chris) Liu; Natalia Maslova; Hui Jia; Qijia Li; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Constructing multi-functional carbon-based aerogels for highly efficient photo-thermal desalination and water purification - Yuqian He; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Enrico Drioli; Jun Ma; Xi Quan Cheng (Desalination, 2024)

Synoptic controls on warm-season O3 pollution in eastern China: A focus on O3-NOx-VOC chemistry - Z.H. Liao; X.C. Jia; Y.L. Qiu; J.N. Quan; Y.B. Pan; P.K. Ma; Z.G. Cheng; Q.Q. Wang (Atmospheric Research, 2024)

Straw and Biochar Amendments Over a Decade Differently Modulates Denitrification Gas Products - Quan Tang; Wenxia Dai; Jiacheng Niu; Jing Wang; Weiqin Yin; Xiaoyuan Yan; Yuji Jiang; Yi Cheng; Shengsen Wang; Xiaozhi Wang (Water, Air, & Soil Pollution, 2024)

Spatial and Temporal Variation of River Water Quality in Yandu District of China - Chaoran Shen; Huihua Lyu; Jianbo Cheng; Yanan Zhang; Quan Ran; Qi Gao; Ying Huang; Rongzhen Wang (Water, Air, & Soil Pollution, 2024)

Correction to: Patterns and determinants of microbial- and plant-derived carbon contributions to soil organic carbon in tea plantation chronosequence - Quan Tang; Wei Li; Wenxia Dai; Jing Wang; Feiyi Zhang; Tim J. Daniell; Yi Cheng; Shengsen Wang; Weiqin Yin; Xiaozhi Wang (Plant and Soil, 2024)

Patterns and determinants of microbial- and plant-derived carbon contributions to soil organic carbon in tea plantation chronosequence - Quan Tang; Wei Li; Wenxia Dai; Jing Wang; Feiyi Zhang; Tim J. Daniell; Yi Cheng; Shengsen Wang; Weiqin Yin; Xiaozhi Wang (Plant and Soil, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Boosting seawater denitrification in an electrochemical flow cell - Ding Li; Shuang-Cheng Jiang; Jia-Fang Xie; Jian Zhang; Ying-Lian Zheng; Quan-Bao Zhao; Han-Qing Yu (Water Research, 2024)

Study on the propagation characteristics of seismic waves perpendicular to the earth-rock dam axis - Hao Xu; Yu-Quan Zong; Jiang-Ping Liu; Xiao-Huan Jiang; Fei Cheng (Soil Dynamics and Earthquake Engineering, 2024)

Strong upwards transport of HONO in daytime over urban area of Beijing, China - Linhui Lan; Jiannong Quan; Pengkun Ma; Yubing Pan; Chaofan Lian; Weigang Wang; Zhiheng Liao; Qianqian Wang; Zhigang Cheng; Lindong Dai; Xingcan Jia; Xiaoling Zhang (Science of The Total Environment, 2024)

T cell senescence may contribute to immunothrombosis via Th17 immune transition in COVID-19 - Wenxing Li; Rui Qian; Zhaoming Zhou; Lei Wen; Quan Yin; Xiang Zhou; Xiaowei Li; Jie Cheng; Xinlu Zhang; Xin Zeng; Zhuoya Wang; Yingying Huang; et al. (Science Bulletin, 2024)

Multicentennial-scale coupling of the East Asian monsoon to North Atlantic climates during the Last Glacial Maximum - Yingfang Cui; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Quan Wang; Zhenjun Wang; Jianshun Chen; Hai Cheng; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Understanding future water-carbon-land coupled systems in the era of COP 27: The case of the Hanjiang river Basin, China - Kai Zhu; Yufeng Cheng; Quan Zhou; Hossein Azadi (Journal of Cleaner Production, 2024)

Response of phytoplankton community to dissolved organic matter composition and lake trophic state - Yadi Ai; Hongguang Cheng; Weici Quan; Qiongyi Wang; Yiwei Gong; Kaiming Yang; Yuxi Wu; Jiawen Zhang; Di Huang (Journal of Environmental Management, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Rapid photochromism and water-driven ultra-fast fading of cellulose-based composite hydrogels enabled by sodium tungstate - Lingqi Quan; Zhiqi Wang; Yu Zhong; Yiqiang Wu; Hui Zhao; Yan Mi; Fangchao Cheng (Chemical Engineering Journal, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Improving key gene expression and di-n-butyl phthalate (DBP) degrading ability in a novel Pseudochrobactrum sp. XF203 by ribosome engineering - Yunchang Xie; Nai-Xian Feng; Li Huang; Miaoer Wu; Cheng-Xuan Li; Fantao Zhang; Yunhong Huang; Quan-Ying Cai; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Boosting peroxodisulfate activation by MIL-68(Fe) derived magnetic Fe3S4 nanosheets: Key role of sulfur vacancy - Feiyang Luo; Cheng Peng; Xinyu Chen; Wenjun Quan; Guohua Du; Jingjing Zhao; Xiaoxu Bo; Shaoyun Shan; Xinggen Yuan; Yanyan Deng; Tianding Hu (Journal of Environmental Chemical Engineering, 2024)

Extraction effects of eight deep eutectic solvents on dianhong black tea: From chemical composition analysis to antioxidant and α-glucosidase inhibitory assessments - Zixin Zhao; Mingchun Wen; Zongde Jiang; Shengxiao Su; Yong-Quan Xu; Zisheng Han; Yong Cheng; Mengting Zhu; Liang Zhang (Food Bioscience, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Engineering PD-L1 targeted liposomal canagliflozin achieves multimodal synergistic cancer therapy - Simeng Wang; Mengjun Sui; Quan Chen; Jiahua Guo; Huini Yang; Ye Zhou; Meiju Ji; Yangyang Cheng; Peng Hou (Chemical Engineering Journal, 2024)

Deep insights into the enhanced waste active sludge lysis by MoS2 and Fe2+ co-activated persulfate - Ting-Ting Zhang; Zun-Jing Lv; Quan-Bao Zhao; Jia-Cheng E. Yang; Zhi-Long Ye; Xiao-Fang Pan; Yu-Ming Zheng (Chemical Engineering Journal, 2024)

Physiological and gene expression responses of Protohermes xanthodes (Megaloptera: Corydalidae) larvae to imidacloprid - Mao-Zhou Xu; Yu-Tong Li; Cheng-Quan Cao (The Science of Nature, 2024)

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Unveiling ammonium concentration ranges that determine competition for mineral nitrogen among soil nitrogen transformations under increased carbon availability - Zhaoxiong Chen; Yu Liu; Liangping Wu; Jing Wang; Ahmed S. Elrys; Yves Uwiragiye; Quan Tang; Hang Jing; Zucong Cai; Christoph Müller; Yi Cheng (Soil Biology and Biochemistry, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Investigation of Toxoplasma gondii Infection in Yunnan Semi-fine Wool Sheep (Ovis aries) and wild Rodents in Yunnan, China - Zhao Li; Wen-Jie Cheng; Cai-Qin Deng; Meng-Ling Deng; Hai-Bo Peng; Xing-Quan Zhu; Feng-Cai Zou (Acta Parasitologica, 2024)

Dynamics and scale variations of blooms of Phaeocystis globosa “giant colony” ecotype and key environmental factors in the Beibu Gulf, China - Zhuang Niu; Jin-Xiu Wang; Qing-Chun Zhang; Chao Liu; Yong-Quan Yuan; Hui-Qun Wang; Fan-Zhou Kong; Ren-Cheng Yu (Marine Pollution Bulletin, 2024)

Orbital- and millennial-scale hydroclimate changes in central China during the last glacial period - Quan Wang; Kan Zhao; Yongjin Wang; Jianshun Chen; Yijia Liang; Yingfang Cui; Qingfeng Shao; Xiumin Zhai; Zhenqiu Zhang; Xinggong Kong; Hai Cheng; R. Lawrence Edwards; et al. (Quaternary Science Reviews, 2024)

Numerical study on the pulsation characteristics of tail cavities under vertical launching conditions - Zeyu Ren; Xiaogang Wang; Shaohua Cheng; Xiaobo Quan; Zhaokai Yu (Ocean Engineering, 2024)

The role of Pleistocene dispersal in shaping species richness of sky island wintergreens from the Himalaya-Hengduan Mountains - Xiao-Juan Cheng; Peter W. Fritsch; Yan-Jun Lin; Guo-Hong Li; Yan-Quan Chen; Ming-Ying Zhang; Lu Lu (Molecular Phylogenetics and Evolution, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Geochemical characteristics and origins of natural gases in the eastern Cote d’Ivoire Basin, West Africa - Li Li; Quan Li; Tao Cheng; Songling Yang; Yong Rao; Xinyu Liu; Wenjing Ding (Acta Oceanologica Sinica, 2024)

Impact of the COVID-19 pandemic on daily travel: Findings from New South Wales, Australia - Bo Du; Cheng Zhang; Tianyang Qu; Qi Wang; Quan Spring Zhou; Tingru Cui; Pascal Perez; Thomas Astell-Burt (Travel Behaviour and Society, 2024)

Enhancing grain shape, thermotolerance, and alkaline tolerance via Gγ protein manipulation in rice - Na Xu; Yuchao Qiu; Xin Cui; Cheng Fei; Quan Xu (Theoretical and Applied Genetics, 2024)

Crystal phase and nanoscale size regulation utilizing the in-situ catalytic pyrolysis of bamboo sawdust in the recycling of spent lithium batteries - Quan Chen; Xuejiao Zhang; Rui Cheng; Huawei Shi; Yanbo Pei; Jingjing Yang; Qing Zhao; Xiaoli Zhao; Fengchang Wu (Waste Management, 2024)

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Relationship of black soldier fly larvae (BSFL) gut microbiota and bioconversion efficiency with properties of substrates - Yu Wang; Jiawei Quan; Xiang Cheng; Chunxing Li; Zengwei Yuan (Waste Management, 2024)

C/N ratio of high-organic C materials is a poor predictor of microbial nitrate immobilization potential in a nitrate-rich soil: An 15N incubation study - Zhaoxiong Chen; Huimin Zhang; Xiaoshun Tu; Jing Wang; Ahmed S. Elrys; Quan Tang; Jinbo Zhang; Zucong Cai; Yi Cheng (Soil and Tillage Research, 2024)

Molecular insights into the catabolism of dibutyl phthalate in Pseudomonas aeruginosa PS1 based on biochemical and multi-omics approaches - Huan Du; Ji-Liang Cheng; Zhi-Yong Li; Huai-Ning Zhong; Shuang Wei; Yu-Juan Gu; Can-Can Yao; Miaoyue Zhang; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

A Bayesian benchmark concentration analysis for urinary fluoride and intelligence in adults in Guizhou, China - Tingxu Jin; Tongtong Huang; Tianxue Zhang; Quan Li; Cheng Yan; Qian Wang; Xiufang Chen; Jing Zhou; Yitong Sun; Wenqing Bo; Ziqi Luo; Haodong Li; et al. (Science of The Total Environment, 2024)

Interfacial OOH* mediated Fe(II) regeneration on the single atom Co-N-C catalyst for efficient Fenton-like processes - Bao-Gang Fu; Xiangtong Zhou; Yilin Lu; Wen-Zhu Quan; Chunmei Li; Liang Cheng; Xiang Xiao; Yang-Yang Yu (Journal of Hazardous Materials, 2024)

Relative contributions of main factors to water levels in Wuchengxiyu Region, China - Zhantuo Xu; Cheng Gao; Quan Quan; Manqiu Hao; Qian Wang; Liangliang She; Yuquan Zhang; Bohua Wu (Journal of Cleaner Production, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

Evaluation of benefits and risks of immunosuppressive drugs in biomaterial-based neural progenitor cell transplantation for spinal cord injury repair - Bo Guo; Xinhao Zhao; Yunlong Zou; Xiaokang Cheng; Zheng Sun; Xiaoyu Xue; Man Yin; Chen Jin; Zhenni Chen; Rui Quan; Wenbin Liu; Bin Chen; et al. (Chemical Engineering Journal, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

A New Perspective on the Semi-quantitative Meso-structural Failure Mechanism of Deep Weak Interlayer Zone Under Different Stress Paths - Shu-Qian Duan; Po Gao; Ding-Ping Xu; Bei Cao; Guo-feng Liu; Quan Jiang; Shi-Li Qiu; Jie-Cheng Xiong (Rock Mechanics and Rock Engineering, 2024)

Observation of D-class topology in an acoustic metamaterial - Shi-Qiao Wu; Wenting Cheng; Xiao-Yu Liu; Bing-Quan Wu; Emil Prodan; Camelia Prodan; Jian-Hua Jiang (Science Bulletin, 2024)

Functionalized-nanoparticles/silk fibroin coating with anti-adhesive and photothermal capabilities to prevent implant-associated infections - Kecheng Quan; Yupu Lu; Zhinan Mao; Shuren Wang; Xiaoxiang Ren; Chunhao Yu; Ting Zhang; Jing-Jun Nie; Yan Cheng; Dafu Chen; Yufeng Zheng; Dandan Xia (Chemical Engineering Journal, 2024)

Reverse diversity–biomass patterns in grasslands are constrained by climates and stoichiometry along an elevational gradient - Jiankun Bai; Chunyan Long; Xin Quan; Chang Liao; Deping Zhai; Yong Bao; Xiuxian Men; Dandan Zhang; Xiaoli Cheng (Science of The Total Environment, 2024)

High organic aerosol in the low layer over a rural site in the North China Plain (NCP): Observations based on large tethered balloon - Jiannong Quan; Juntao Huo; Chenglong Zhang; Yubing Pan; Pengkun Ma; Zhiheng Liao; Zhigang Cheng; Xingcan Jia; Qianqian Wang; Qingyan Fu; Yujing Mu; Fei Hu (Science of The Total Environment, 2024)

Detecting multidecadal variation of short-term drought risk by combining frequency analysis and Fourier transformation methods: A case study in the Yangtze River Basin - Kaijie Zou; Lei Cheng; Quan Zhang; Shujing Qin; Pan Liu; Mengqi Wu (Journal of Hydrology, 2024)

Optimizing the algae-bacteria biofilm reactor for imidacloprid wastewater treatment: An evaluation of hydraulic retention times for enhanced efficiency and energy savings - Yongtao Cheng; Linghui Quan; Ashiwin Vadiveloo; Lie Yang; Abdullah A. Saber; Shubin Lan; Sara S. A. Alsaif; Zhaojun Wang; Li Wu (Journal of Environmental Management, 2024)

Upcycling of hazardous plastic waste by CO2 transformation-enhanced steam reforming over MgO-promoted Ni/C bifunctional catalyst - Xuesong Zhang; Kejie Wang; Fangqi Liu; Ge Kong; Guanya Ji; Yuan Jiang; Guanyu Zhang; Quan Liu; Qing Cheng; Tianqi Cao; Hongkang Liu; Xin Zhang; et al. (Chemical Engineering Journal, 2024)

Regional transport of aerosol above boundary layer and its radiation effect trigger severe haze pollution in Beijing - Xingcan Jia; Jiannong Quan; Xiujuan Zhao; Yubing Pan; Zhigang Cheng; Ying Wei; Zhiheng Liao; Youjun Dou; Pengkun Ma (Atmospheric Research, 2024)

Moment Tensor and Stress Field Inversions of Mining-Induced Seismicity in A Thick-Hard Roof Zone - Chun-Hui Song; Cai-Ping Lu; Hai-Quan Liu; Jie-Fang Song; Cheng-Yu Liu; Hua-Wei Cui; Jin-Rui Zhang (Rock Mechanics and Rock Engineering, 2024)

Awakening soil microbial utilization of nitrate by carbon regulation to lower nitrogen pollution - Quan Tang; Jing Wang; Miaomiao Cao; Zhaoxiong Chen; Xiaoshun Tu; Ahmed S. Elrys; Hang Jing; Xiaozhi Wang; Zucong Cai; Christoph Müller; Tim J. Daniell; Xiaoyuan Yan; et al. (Agriculture, Ecosystems & Environment, 2024)

Insights into the molecular network underlying phytotoxicity and phytoaccumulation of ciprofloxacin - Hai-Ming Zhao; He-Biao Huang; Zhen-Xuan Zhan; Yao-Yao Ye; Ji-Liang Cheng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Yunchang Xie; Ce-Hui Mo (Science of The Total Environment, 2024)

Cattle manure hydrochar posed a higher efficiency in elevating tomato productivity and decreasing greenhouse gas emissions than plant straw hydrochar in a coastal soil - Xiao Wang; Qingxian Kong; Yadong Cheng; Chenghao Xie; Yuan Yuan; Hao Zheng; Xueyang Yu; Hui Yao; Yue Quan; Xiangwei You; Chengsheng Zhang; Yiqiang Li (Science of The Total Environment, 2024)

A study on non-destructive detecting method for carbon particles inside metal structures based on X-ray imaging with contrast agents - Yu Chen; Xinyu Liu; Zhenhai Wang; Bowen Cheng; Quan Zhu (Fuel, 2024)

Retraction Note: SOCS3 inhibits insulin signaling in porcine primary adipocytes - Shuang-Juan Yang; Cheng-Quan Xu; Jiang-Wei Wu; Gong-She Yang (Molecular and Cellular Biochemistry, 2024)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

The alkaloids with neuroprotective effect from the root bark of Ailanthus altissima - Qing Shao; Tian-Yi Li; Wei Quan; Hui Wang; Ke-Yu Yan; Peng-Cheng Qiu; Hai-Feng Tang; Yun-Yang Lu (Natural Product Research, 2023)

Synthesis and evaluation of in vitro and in vivo anti -Toxoplasma gondii activity of tetraoxane-substituted ursolic acid derivatives - Ya-Lan Wang; Li-Li Jin; Xu Cheng; Wei-Feng Yan; Hao Deng; Qing-Kun Shen; Zhe-Shan Quan; Chun-Mei Jin; Chang-Hao Zhang (Natural Product Research, 2023)

Revealing the effects of fermented food waste on the growth and intestinal microorganisms of black soldier fly (Hermetia illucens) larvae - Jiawei Quan; Yu Wang; Xiang Cheng; Chunxing Li; Zengwei Yuan (Waste Management, 2023)

Analysis of leaf economics sheds light on the heterophylly and ecological strategies of Paleocene Ginkgo leaves from Henan Province, China - Qijia Li; Bingshan Niu; Yusheng (Christopher) Liu; Hui Jia; Yu Li; Li Xu; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Catalytic hydrothermal co-liquefaction of sewage sludge and agricultural biomass for promoting advanced biocrude production - Guanyu Zhang; Quan Liu; Xintong Li; Ge Kong; Tianqi Cao; Qing Cheng; Ziyi Zhang; Xuesong Zhang; Lujia Han (Journal of Cleaner Production, 2023)

Proteome reveals the mechanism of selenium-sulfur interaction in regulating isothiocyanate biosynthesis and the physiological metabolism of broccoli sprouts - Yongqi Yin; Xiaolan Quan; Yuwei Cheng; Zhengfei Yang; Jiangyu Zhu; Weiming Fang (Food Chemistry, 2023)

Correction: Microglial Depletion does not Affect the Laterality of Mechanical Allodynia in Mice - Quan Ma; Dongmei Su; Jiantao Huo; Guangjuan Yin; Dong Dong; Kaifang Duan; Hong Cheng; Huiling Xu; Jiao Ma; Dong Liu; Bin Mou; Jiyun Peng; et al. (Neuroscience Bulletin, 2023)

Structural plane recognition from three-dimensional laser scanning points using an improved region-growing algorithm based on the robust randomized Hough transform - Zhi-hua Xu; Ge Guo; Qian-cheng Sun; Quan Wang; Guo-dong Zhang; Run-qing Ye (Journal of Mountain Science, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

CO2-mediated catalytic upcycling of plastic waste for H2-rich syngas and carbon nanomaterials - Xuesong Zhang; Yuan Jiang; Ge Kong; Quan Liu; Guanyu Zhang; Kejie Wang; Tianqi Cao; Qing Cheng; Ziyi Zhang; Guanya Ji; Lujia Han (Journal of Hazardous Materials, 2023)

Twisting two-dimensional photothermal sponges for boosting solar steam generation - Feng Lu; Shao-Lin Wu; Lu-Na Quan; Zhi-Hui Zhong; Hao-Cheng Yang; Ming Xue (Chemical Engineering Journal, 2023)

Enhancing sulfate reduction and hydrogen sulfide removal through gas stripping in the acidogenesis phase of a two-phase anaerobic process - Ting-Ting Zhang; Quan-Bao Zhao; Xiao-Qiong Wu; Cheng Xu; Yu-Ming Zheng; Sheng-Song Yu (Bioresource Technology, 2023)

Observational evidence of the regional transported black carbon in high layer over Beijing - Zhiguo Kang; Pengkun Ma; Jiannong Quan; Xingcan Jia; Zhiheng Liao; Zhigang Cheng; Qianqian Wang; Lindong Dai; Xiujuan Zhao; Ziyin Zhang; Tie Yuan; Yubing Pan (Atmospheric Environment, 2023)

Neuronal Histone Methyltransferase EZH2 Regulates Neuronal Morphogenesis, Synaptic Plasticity, and Cognitive Behavior in Mice - Mei Zhang; Yong Zhang; Qian Xu; Joshua Crawford; Cheng Qian; Guo-Hua Wang; Jiang Qian; Xin-Zhong Dong; Mikhail V. Pletnikov; Chang-Mei Liu; Feng-Quan Zhou (Neuroscience Bulletin, 2023)
The histone methyltransferase enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2)-mediated trimethylation of histone H3 lysine 27 (H3K27me3) regulates neural stem cell proliferation and fate specificity through silencing different gene sets in the central nervous system. Here, we explored the function of EZH2 in early post-mitotic neurons by generating a neuron-specific Ezh2 conditional knockout mouse line. The results showed that a lack of neuronal EZH2 led to delayed neuronal migration, more complex dendritic arborization, and increased dendritic spine density. Transcriptome analysis revealed that neuronal EZH2-regulated genes are related to neuronal morphogenesis. In particular, the gene encoding p21-activated kinase 3 ( Pak3) was identified as a target gene suppressed by EZH2 and H3K27me3, and expression of the dominant negative Pak3 reversed Ezh2 knockout-induced higher dendritic spine density. Finally, the lack of neuronal EZH2 resulted in impaired memory behaviors in adult mice. Our results demonstrated that neuronal EZH2 acts to control multiple steps of neuronal morphogenesis during development, and has long-lasting effects on cognitive function in adult mice.

Development of a surface plasmon resonance based immunosensor for diclofenac quantification in water - Marcela Herrera-Domínguez; Alexander S. Lambert; Gesuri Morales-Luna; Eduardo Pisano; Iris Aguilar-Hernandez; Jürgen Mahlknecht; Quan Cheng; Nancy Ornelas-Soto (Chemosphere, 2023)

The acceleration on decolorization of azo dyes by magnetic lignin-based materials via enhancing the extracellular electron transfer - Rong-ping Chen; Xin-yuan Wei; Cheng-hao Gan; Bing-cai Cai; Wen-jie Xu; Shareen Niyazi; Quan Wang; Lei Yu; Hui-hua Min; Qiang Yong (Journal of Environmental Management, 2023)

New biodegradation degree proxies based on acids and neutral nitrogen- and oxygen-containing compounds characterized by high resolution mass spectrometry - Dongyong Wang; Meijun Li; Dingsheng Cheng; Yebo Du; Quan Shi; Xianli Zou; Qingyao Chen (Fuel, 2023)

Experiment study on reactive powder concrete beams using spirals reinforcement under torsion - Xia Cao; Yong-peng Quan; Yi-cheng Ren; Feng Fu; Qi-zhi Jin; Da-bo He; Yan Zheng (Engineering Structures, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Mineral dust scavenges anthropogenic aerosols in polluted environment - Yubing Pan; Jiannong Quan; Pengkun Ma; Zhiheng Liao; Xingcan Jia; Youjun Dou; Zhigang Cheng; Lei Lei; Yuanyuan Wang; Mei Zheng; Daren Lü; Yinan Wang (Atmospheric Environment, 2023)

MRI radiomics for brain metastasis sub-pathology classification from non-small cell lung cancer: a machine learning, multicenter study - Fuxing Deng; Zhiyuan Liu; Wei Fang; Lishui Niu; Xianjing Chu; Quan Cheng; Zijian Zhang; Rongrong Zhou; Guang Yang (Physical and Engineering Sciences in Medicine, 2023)

Pine pollen: A review of its chemical composition, health effects, processing, and food applications - Yong Cheng; Zhenyu Wang; Wei Quan; Chaoyi Xue; Tao Qu; Tong Wang; Qiuming Chen; Zhaojun Wang; Maomao Zeng; Fang Qin; Jie Chen; Zhiyong He (Trends in Food Science & Technology, 2023)

Performance of a biocrust cyanobacteria-indigenous bacteria (BCIB) co-culture system for nutrient capture and transfer in municipal wastewater - Li Wu; Linghui Quan; Zhikang Deng; Ashiwin Vadiveloo; Yongtao Cheng; Lie Yang; Zulin Zhang; Abdullah A. Saber; Shubin Lan (Science of The Total Environment, 2023)

Multi-objective optimization of chemical process plant layout considering economy and inherent safety - Zi Lin; Lin-Quan Gong; Jing-Jing Xu; Jia-Jia Jiang; Jun-Cheng Jiang (Process Safety and Environmental Protection, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Investigation on supported AlCl3 catalyst in the isomerization of E-1-chloro-3,3,3-trifluoropropene - Jinxin Cheng; Chengping Zhang; Hengdao Quan (Journal of Fluorine Chemistry, 2023)

The status and improvement opportunities towards carbon neutrality of a university campus in China: A case study on energy transition and innovation perspectives - Chenxi Wang; Ashak Mahmud Parvez; Jiayou Mou; Cheng Quan; Jiashuo Wang; Yueying Zheng; Xiang Luo; Tao Wu (Journal of Cleaner Production, 2023)

Microglial Depletion does not Affect the Laterality of Mechanical Allodynia in Mice - Quan Ma; Dongmei Su; Jiantao Huo; Guangjuan Yin; Dong Dong; Kaifang Duan; Hong Cheng; Huiling Xu; Jiao Ma; Dong Liu; Bin Mou; Jiyun Peng; et al. (Neuroscience Bulletin, 2023)

Influence of surface roughness on the development of moss-dominated biocrusts on mountainous rock-cut slopes in West Sichuan, China - Xin-yue Zhao; Mao-qiang Zhao; Pan-pan Wang; Yu-quan Dai; Wan-qiu Pu; Cheng-min Huang (Journal of Mountain Science, 2023)

MiR-3677-3p promotes development and sorafenib resistance of hepatitis B-related hepatocellular carcinoma by inhibiting FOXM1 ubiquitination - Hengzheng He; Jian Zhou; Fahui Cheng; Huijuan Li; Yangya Quan (Human Cell, 2023)

Asymptotic linearized inversion for acoustic variable-tilt transversely isotropic media through elliptic perturbation analysis - Wei Ouyang; Quan Liang; Weijian Mao; Shijun Cheng (Wave Motion, 2023)

Fermentation broth of food waste: A sustainable electron donor for perchlorate biodegradation - Lijie Cheng; Ningbo Gao; Cui Quan (Waste Management, 2023)

China's wastewater treatment: Status quo and sustainability perspectives - Chunhui Zhang; Bingxu Quan; Jiawei Tang; Kaipeng Cheng; Yuanhui Tang; Wenlong Shen; Peidong Su; Chunyu Zhang (Journal of Water Process Engineering, 2023)

Characteristics and comparisons of the aerobic and anaerobic denitrification of a Klebsiella oxytoca strain: Performance, electron transfer pathway, and mechanism - Cheng-jia Ju; Shareen Niyazi; Wen-yin Cao; Quan Wang; Rong-ping Chen; Lei Yu (Journal of Environmental Management, 2023)

Phosphorus amendment alters soil arbuscular mycorrhizal fungal functional guild compositions in a subtropical forest - Quan-Cheng Wang; Sheng-Sheng Jin; Shanshan Liu; Ge Song; Chunjian Duan; Peng-Peng Lü; Pulak Maitra; Lin Xie; Yongxin Lin; Hang-Wei Hu; Ji-Zheng He; Yong Zheng (Journal of Soils and Sediments, 2023)

Experimental Study on Motion Characteristics of Cavity Attached to the Tail of Underwater Vehicle - Xiongliang Yao; Zhaoyu Qu; Guihui Ma; Nana Yang; Xiaobo Quan; Shaohua Cheng (Journal of Marine Science and Engineering, 2023)
The formation and development of an attached cavity at the tail of an underwater moving vehicle involves a complex multiphase flow, which determines the load characteristics and motion stability of the vehicle. In this study, an experimental method was used to explore the formation process and motion characteristics of the cavity at the tail of the vehicle, and a pressure sensor installed at the tail of the model was used to establish the relationship between the evolution of the tail attachment cavity and transient pressure. The study found that the process of pulling and breaking the attached cavity was accompanied by the generation of bidirectional jets, and reducing the cavitation number could weaken the occurrence of jet impact. When the ventilation flow reaches the critical value Q¯in = 1.28, the cavity pulsates. In addition, increasing the ventilation flow does not increase the size of the tail cavity, and the length of the cavity at the closure increases with the decrease of the cavitation number.

The tanshinones from the plant of Salvia miltiorrhiza - Jian-Shuang Jiang; Quan-chang Gu; Zi-Ming Feng; Xiang Yuan; Xu Zhang; Pei-Cheng Zhang; Ya-Nan Yang (Phytochemistry, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Fire-safe epoxy composite realized by MXenes based nanostructure with vertically arrayed MOFs derived from interfacial assembly strategy - Shui Yu; Chao Cheng; Keji Li; Junling Wang; Zhirong Wang; Haobo Zhou; Wei Wang; Yan Zhang; Yan Quan (Chemical Engineering Journal, 2023)

Ultra-thin CoNi0.2P nanosheets for plastics and biomass participated hybrid water electrolysis - Xiao-Hui Wang; Ze-Nong Zhang; Zhe Wang; Yu Ding; Quan-Guo Zhai; Yu-Cheng Jiang; Shu-Ni Li; Yu Chen (Chemical Engineering Journal, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Extreme storm events shift DOC export from transport-limited to source-limited in a typical flash flood catchment - Hang Su; Lei Cheng; Yue Wu; Shujing Qin; Pan Liu; Quan Zhang; Shujie Cheng; Yuran Li (Journal of Hydrology, 2023)

The role of anthraquinone-2-sulfonate on intra/extracellular electron transfer of anaerobic nitrate reduction - Lei Yu; Cheng-jia Ju; Kai-yan Jing; Zi-yang Wang; Shareen Niyazi; Quan Wang (Journal of Environmental Management, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Fine mapping of KLW1 that conditions kernel weight mainly through regulating kernel length in wheat (Triticum aestivum L.) - Yang Yang; Zhongxin Kong; Quan Xie; Haiyan Jia; Wenshuo Huang; Liwei Zhang; Ruiru Cheng; Zibo Yang; Xiaolei Qi; Guangde Lv; Yong Zhang; Yixuan Wen; et al. (Theoretical and Applied Genetics, 2023)

Regional allocation of carbon emission quotas in China under the total control target - Xiaojuan Cheng; Shiqi Ouyang; Chunguang Quan; Guiju Zhu (Environmental Science and Pollution Research, 2023)

Efficient removal of thiamethoxam by freshwater microalgae Scenedesmus sp. TXH: Removal mechanism, metabolic degradation and application - Linghui Quan; Yongtao Cheng; Jiping Wang; Yulin Chen; Diantong Li; Shiqi Wang; Bolin Li; Zulin Zhang; Lie Yang; Li Wu (Journal of Environmental Management, 2023)

Surface display of major capsid protein on Bacillus subtilis spores against largemouth bass virus (LMBV) for oral administration - Quan Wang; Xia Liang; Yunshang Ning; Shijia Liu; Zengjian Liang; Zemiao Zhang; Yingjing Chen; Jinqiao Cao; Fubao Wang; Lingfeng Lan; Guangzhao Cheng; Youhua Huang; et al. (Fish & Shellfish Immunology, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Correction to: Matrine suppresses expression of adhesion molecules and chemokines as a mechanism underlying its therapeutic effect in CNS autoimmunity - Quan-Cheng Kan; Lin Zhu; Nan Liu; Guang-Xian Zhang (Immunologic Research, 2023)

What determines the time lags of sap flux with solar radiation and vapor pressure deficit? - Liuliu Wan; Quan Zhang; Lei Cheng; Yujie Liu; Shujing Qin; Jijun Xu; Yongqiang Wang (Agricultural and Forest Meteorology, 2023)

Efficient methods of seedling culture and cultivation of the economic macroalga Scytosiphon lomentaria (Phaeophyta): A systematic review - Di Zhang; Cheng-Ying Luo; Ming-Yu Zhong; Zi-Min Hu; Quan-Sheng Zhang (Aquaculture, 2023)

Utilization of current pyrolysis technology to convert biomass and manure waste into biochar for soil remediation: A review - Shimeng Tan; Guoying Zhou; Quan Yang; Shengbo Ge; Junang Liu; Yoke Wang Cheng; Peter Nai Yuh Yek; Wan Adibah Wan Mahari; Sieng Huat Kong; Jo-Shu Chang; Christian Sonne; William Woei Fong Chong; et al. (Science of The Total Environment, 2023)

Experimental and numerical simulation study on thermal decomposition model of ammonium nitrate - Lin-Quan Gong; Jia-Jia Jiang; Jun-hui Gong; Yong Pan; Jun-Cheng Jiang (Process Safety and Environmental Protection, 2023)

Mechanochemical modified nitrogen-rich biochar derived from shrimp shell: Dominant mechanism in pyridinic-N for aquatic methylene blue removal - Ming Wang; Jinlong Yan; Yumeng Xu; Xiangqian Zhou; Yusen Diao; Hui Wang; Jiahao Bian; Cheng Liu; Guixiang Quan (Journal of Environmental Management, 2023)

Overexpressing SIRT6 can Attenuate the Injury of Intracerebral Hemorrhage by Down-Regulating NF-kB - Jing Cheng; Yan-Qin Fan; Wen-Fei Zhang; Guo Zhang; Kuo Zeng; Zhang Ye; Dan Zhao; Li-Quan Wu; Zhi-Biao Chen (NeuroMolecular Medicine, 2023)

Abandoned land identification in karst mountain area based on time series SAR characteristics at geo-parcels scale - Zhong-fa Zhou; Ling-yu Wang; Quan Chen; Jian-cheng Luo; Xin Zhao; Shu Zhang; Wen-hui Zhang; Juan Liao; Zhi-jun Lyu (Journal of Mountain Science, 2023)

Stabilizing zinc deposition through solvation sheath regulation and preferential adsorption by electrolyte additive of lithium difluoro(oxalato)borate - Weijun Zhou; Minfeng Chen; Yuhui Quan; Jing Ding; Hanlin Cheng; Xiang Han; Jizhang Chen; Bo Liu; Siqi Shi; Xinwu Xu (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Meteorological and chemical controls on surface ozone diurnal variability in Beijing: A clustering-based perspective - Zhiheng Liao; Yubing Pan; Pengkun Ma; Xingcan Jia; Zhigang Cheng; Qianqian Wang; Youjun Dou; Xiujuan Zhao; Jinqiang Zhang; Jiannong Quan (Atmospheric Environment, 2023)

Mixing state of refractory black carbon in the residual layer over megacity - Zhiguo Kang; Pengkun Ma; Jiannong Quan; Zhiheng Liao; Yubing Pan; Hang Liu; Xiaole Pan; Youjun Dou; Xiujuan Zhao; Zhigang Cheng; Qianqian Wang; Tie Yuan; et al. (Atmospheric Environment, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Effect of hydrodynamics on the transformation of nitrogen in river water by regulating the mass transfer performance of dissolved oxygen in biofilm - Mei Pan; Haizong Li; Xiangyun Han; Guixiang Quan; Weixing Ma; Qingyuan Guo; Xuan Li; Bairen Yang; Cheng Ding; Yuxi Chen; Tao Yun; Jiaojiao Qin; et al. (Chemosphere, 2023)

Experimental study on ventilated cavity flow at the tail of underwater vehicle under low surface tension - Zhaoyu Qu; Nana Yang; Guihui Ma; Xiongliang Yao; Wangkai Zhang; Hongtu Zhang; Shaohua Cheng; Xiaobo Quan; Yingyu Chen (Ocean Engineering, 2023)

Effect of multi-type oxides on the catalytic pyrolysis behaviors of 5-amino-1H-tetrazole - Jiu Chen; Quan Liu; Xian-Zhao Song; Si-Yuan Zhou; Bin Li; Li-Feng Xie; Guang-Cheng Yang; Cheng-Yan Cao; Song Lu; Dan Zhang (Fuel, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

High-performance organic photodetectors enabled by a refined fibrillar multiphase morphology - Huilei Quan; Zhiming Zhong; Tianyu Hao; Kang An; Wenkai Zhong; Cheng Wang; Feng Liu; Lei Ying; Fei Huang (Chemical Engineering Journal, 2023)

Investigation on frost heaving stress (FHS) of porous cement concrete exposed to freeze-thaw cycles - Jun Chen; Cheng Zhao; Quan Liu; Xijun Shi; Zhenhao Sun (Cold Regions Science and Technology, 2023)

Ice-volume and insolation influences on hydroclimate changes in central eastern China during the antepenultimate glacial period - Quan Wang; Shayue Yuan; Yijia Liang; Kan Zhao; Qingfeng Shao; Zhenqiu Zhang; Junji Zhu; Xinggong Kong; Yongjin Wang; Jianghu Lan; Hai Cheng; Chengwei Xia; et al. (Science China Earth Sciences, 2023)

Production and characterization of novel thermo- and organic solvent–stable keratinase and aminopeptidase from Pseudomonas aeruginosa 4–3 for effective poultry feather degradation - Xiao-Dong Pei; Fan Li; Shi-Yang Yue; Xiao-Ni Huang; Tian-Tian Gao; Dao-Quan Jiao; Cheng-Hua Wang (Environmental Science and Pollution Research, 2023)

A strategy for screening and identification of new amino acid-conjugated bile acids with high coverage by liquid chromatography-mass spectrometry - Yan-Zhen Wang; Peng-Cheng Mei; Pei-Rong Bai; Na An; Jin-Gang He; Jie Wang; Quan-Fei Zhu; Yu-Qi Feng (Analytica Chimica Acta, 2023)

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Genome-wide association study of SARS-CoV-2 infection in Chinese population - Jie Fan; Quan-Xin Long; Ji-Hua Ren; Hao Chen; Meng-Meng Li; Zheng Cheng; Juan Chen; Li Zhou; Ai-Long Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Distinctive Roles of Wnt Signaling in Chondrogenic Differentiation of BMSCs under Coupling of Pressure and Platelet-Rich Fibrin - Baixiang Cheng; Fan Feng; Fan Shi; Jinmei Huang; Songbai Zhang; Yue Quan; Teng Tu; Yanli Liu; Junjun Wang; Ying Zhao; Min Zhang (Tissue Engineering and Regenerative Medicine, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Comparative plastid genome analyses of Rosa: Insights into the phylogeny and gene divergence - Cheng Zhang; Shi-Qi Li; Huan-Huan Xie; Jian-Quan Liu; Xin-Fen Gao (Tree Genetics & Genomes, 2022)

Sevoflurane inhibits the malignant phenotypes of glioma through regulating miR-146b-5p/NFIB axis - Haili Wang; Guofang Cheng; Lili Quan; Haibo Qu; Ailing Yang; Jiangge Ye; Yuanbo Feng; Xiaofang Li; Xiaoli Shi; Hua Pan (Metabolic Brain Disease, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

First report of a crinivirus infecting mulberry (Morus alba L.) in China - Peng Zhang; Yu Ma; Tao-Tao Han; William Kojo Smith; Jing Yu; Yong-Yuan Cheng; Quan-You Lu (Journal of Plant Pathology, 2022)

Exploring tourism networks in the Guangxi mountainous area using mobility data from user generated content - Yan-hua Liu; Jian-quan Cheng; Yu-lan Lyu (Journal of Mountain Science, 2022)

Characterization of a strong constitutive promoter from paper mulberry vein banding virus - William K. Smith; Yu Ma; Jing Yu; Yong-Yuan Cheng; Peng Zhang; Tao-Tao Han; Quan-You Lu (Archives of Virology, 2022)

MiR-590-5p inhibits pathological hypertrophy mediated heart failure by targeting RTN4 - Ping Fan; Likun Zhang; Tianyu Cheng; Jing Wang; Junyun Zhou; Li Zhao; Cuie Hua; Quan Xia (Journal of Molecular Histology, 2021)

The mTOR/NF-κB Pathway Mediates Neuroinflammation and Synaptic Plasticity in Diabetic Encephalopathy - Ting Xu; Jiao Liu; Xin-rui Li; Yinghua Yu; Xuan Luo; Xian Zheng; Yuan Cheng; Pei-quan Yu; Yi Liu (Molecular Neurobiology, 2021)

An underlying mechanism of qE deficiency in marine angiosperm Zostera marina - Wei Zhao; Quan Sheng Zhang; Ying Tan; Zhe Liu; Ming Yu Ma; Meng Xin Wang; Cheng Ying Luo (Photosynthesis Research, 2021)

N6-methyladenine DNA Demethylase ALKBH1 Regulates Mammalian Axon Regeneration - Qiao Li; Cheng Qian; Harry Feng; Tyger Lin; Qingsan Zhu; Ying Huang; Feng-Quan Zhou (Neuroscience Bulletin, 2021)

New 40Ar/39Ar and (U-Th)/He dating for the Zhunuo porphyry Cu deposit, Gangdese belt, southern Tibet: implications for pulsed magmatic-hydrothermal processes and ore exhumation and preservation - Xiang Sun; Cheng-Biao Leng; Pete Hollings; Qing-Jie Song; Ru-Yue Li; Xiu-Quan Wan (Mineralium Deposita, 2021)

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Assessing the Influence of Aerosol on Radiation and Its Roles in Planetary Boundary Layer Development - Zhigang Cheng; Yubing Pan; Ju Li; Xingcan Jia; Xinyu Zhang; Pengkun Ma; Qianqian Wang; Junxia Dou; Jingjiang Zhang; Jiannong Quan (Journal of Meteorological Research, 2021)

Role and application of quorum sensing in anaerobic ammonium oxidation (anammox) process: A review - Quan Zhang; Nian-Si Fan; Jin-Jin Fu; Bao-Cheng Huang; Ren-Cun Jin (Critical Reviews in Environmental Science and Technology, 2021)

An Insight into the Excavation-Induced Stress Paths on Mechanical Response of Weak Interlayer Zone in Underground Cavern Under High Geostress - Shu-Qian Duan; Quan Jiang; Guo-Feng Liu; Jie-Cheng Xiong; Po Gao; Ding-Ping Xu; Ming-Yu Li (Rock Mechanics and Rock Engineering, 2021)

Relationship of extreme precipitation, surface air temperature, and dew point temperature across the Tibetan Plateau - Zhiwei Yong; Junnan Xiong; Zegen Wang; Weiming Cheng; Jiawei Yang; Quan Pang (Climatic Change, 2021)

Degradation stage effects on vegetation and soil properties interactions in alpine steppe - Cheng-yang Li; Fei Peng; Xian Xue; Chi-min Lai; Wen-juan Zhang; Quan-gang You; Xiao-jie Chen; Xue-qin Zhang; Tao Wang (Journal of Mountain Science, 2021)

High-sulfidation veins in the Jiama porphyry system, South Tibet - Shi-Ji Zheng; Hong Zhong; Zhong-Jie Bai; Zhong-Kun Zhang; Cheng-Quan Wu (Mineralium Deposita, 2021)

Numerical simulations of incompressible fluid flow in synthetic fractures using lattice Boltzmann method - Guan Rong; Long Cheng; Junsong Quan; Yaosheng Tan; Renhui He; Jie Tan (Arabian Journal of Geosciences, 2020)

Histogram of maximal point-edge orientation for multi-source image matching - Quan Wu; Guili Xu; Yuehua Cheng; Wende Dong; Limin Ma; Zhenhua Li (International Journal of Remote Sensing, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

First report of tobacco vein banding mosaic virus infecting Solanum lyratum Thunb in China - Jian Zhang; Yong-Yuan Cheng; Lei Yang; Xin Sun; Jing Yu; Quan-You Lu (Journal of Plant Pathology, 2020)

V3 protein encoded by mulberry crinkle leaf virus acts as a pathogenicity determinant in Nicotiana benthamiana - Quan-You Lu; Jing Yu; Yong-Yuan Cheng; Xin Sun; Lei Yang (European Journal of Plant Pathology, 2020)

Brain-Wide Shape Reconstruction of a Traced Neuron Using the Convex Image Segmentation Method - Shiwei Li; Tingwei Quan; Hang Zhou; Qing Huang; Tao Guan; Yijun Chen; Cheng Xu; Hongtao Kang; Anan Li; Ling Fu; Qingming Luo; Hui Gong; et al. (Neuroinformatics, 2020)

Effects of culture medium composition and PEG on hyperhydricity in Dendrobium officinale - Hongyang Gao; Danyun Xu; Huiju Zhang; Xuanxuan Cheng; Quan Yang (In Vitro Cellular & Developmental Biology - Plant, 2020)

Fluoride-induced rectal barrier damage and microflora disorder in mice - Hong-wei Wang; Cheng-yi Miao; Jing Liu; Yan Zhang; Shi-quan Zhu; Bian-hua Zhou (Environmental Science and Pollution Research, 2020)

The linkage between methane production activity and prokaryotic community structure in the soil within a shale gas field in China - Yan-Qin Wang; Guang-Quan Xiao; Yong-Yi Cheng; Ming-Xia Wang; Bo-Ya Sun; Zhi-Feng Zhou (Environmental Science and Pollution Research, 2020)

Molecular and morphological evidence for hybrid origin and matroclinal inheritance of an endangered wild rose, Rosa × pseudobanksiae (Rosaceae) from China - Cheng Zhang; Shi-Qi Li; Yu Zhang; Zhang-Ming Zhu; Jian-Quan Liu; Xin-Fen Gao (Conservation Genetics, 2020)

The root endophytic fungus Serendipita indica improves resistance of Banana to Fusarium oxysporum f. sp. cubense tropical race 4 - Chunzhen Cheng; Dan Li; Quan Qi; Xueli Sun; Mensah Raphael Anue; Bodjrenou Mahoudjro David; Yongyan Zhang; Xiangyang Hao; Zihao Zhang; Zhongxiong Lai (European Journal of Plant Pathology, 2020)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

5-Aminolevulinic acid (ALA) promotes primary root elongation through modulation of auxin transport in Arabidopsis - Yuyan An; Danxuan Cheng; Zhixiong Rao; Yongping Sun; Quan Tang; Liangju Wang (Acta Physiologiae Plantarum, 2019)

Effects of law enforcement and community outreach on mammal diversity in a biodiversity hotspot - Cheng Chen; Rui‐Chang Quan; Guanghong Cao; Hongpei Yang; A. Cole Burton; Michael Meitner; Jedediah F. Brodie (Conservation Biology, 2019)
Management activities such as law enforcement and community outreach are thought to affect conservation outcomes in protected areas, but their importance relative to intrinsic environmental characteristics of the parks and extrinsic human pressures surrounding the parks have not been explored. Furthermore, it is not clear which is more related to conservation outcomes—the management itself or local people's perceptions of the management. We measured objective (reports by park staff) and subjective (reports by local people) levels of community outreach and law enforcement based on responses to 374 questionnaires. We estimated mammal abundance and diversity of 6 protected areas based on data from 115 camera traps in Xishuangbanna, southwest China, a biodiversity hotspot with high hunting and land‐conversion pressures. We then examined correlations among them and found that local people's perception of law enforcement was positively related to the local abundance of 2 large, hunted species, wild boar ( Sus scrofa ) (β = 15.22) and muntjac ( Muntiacus vaginalis ) (β = 14.82), but not related to the abundance of smaller mammals or to objective levels of enforcement. The subjective frequency of outreach by park staff to local communities (β = 3.42) and park size (β = 3.28) were significantly and positively related to mammal species richness, whereas elevation, human population density, and subjective frequency of law enforcement were not. We could not conclude that community outreach and law enforcement were directly causing increased mammal abundance and diversity. Nevertheless, the patterns we detected are some of the first empirical evidence consistent with the idea that biodiversity in protected areas may be more positively and strongly related to local perceptions of the intensity of park management than to either intrinsic (e.g., elevation, park size) or extrinsic (e.g., human population density) environmental factors.

Association mapping and favourable QTL alleles for fibre quality traits in Upland cotton (Gossypium hirsutum L.) - Cheng-Guang Dong; Juan Wang; Yu Yu; Bao-Cheng Li; Quan-Jia Chen (Journal of Genetics, 2018)

Nocardia zhihengii sp. nov., an actinobacterium isolated from rhizosphere soil of Psammosilene tunicoides - Mei-Juan Huang; Min Xiao; Manik Prabhu Narsing Rao; Tao Cheng; Yan-Yu Yang; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Hai-Quan Huang; Wen-Jun Li (Antonie van Leeuwenhoek, 2018)

Genomic characterizations of H4 subtype avian influenza viruses from live poultry markets in Sichuan province of China, 2014–2015 - Chuansong Quan; Ting Huang; Xiuwei Chen; Jie Zhang; Qianli Wang; Cheng Zhang; Tiyan Zhang; Lijun Zhou; Liumei Shu; Chunrong Long; Lei Yang; Xunbo Du; et al. (Science China Life Sciences, 2018)

Identification of Neoscytalidium dimidiatum causing canker disease of pitaya in Hainan, China - Min Xu; Yun Peng; Zhao Qi; Zhen Yan; Lu Yang; Meng-Die He; Qing-Xiu Li; Cheng-Li Liu; Yun-Ze Ruan; Shuang-Shuang Wei; Jun Xie; You-Quan Xia; et al. (Australasian Plant Pathology, 2018)

Modeling and multi-objective optimization for ANAMMOX process under COD disturbance using hybrid intelligent algorithm - Bin Xie; Yong-wen Ma; Jin-quan Wan; Yan Wang; Zhi-cheng Yan; Lin Liu; Ze-yu Guan (Environmental Science and Pollution Research, 2018)

GbABR1 is associated with Verticillium wilt resistance in cotton - Yujia Liu; Xin Liu; Lu Long; Weina Wang; Quan Sun; Bo Li; Chenxiao Wang; Jieru Cheng; Yuanyuan Zhang; Yuanhui Xie; Lingling Xu; Runkuan Qin; et al. (Biologia, 2018)

The effect of electron competition on chromate reduction using methane as electron donor - Pan-Long Lv; Liang Zhong; Qiu-Yi Dong; Shi-Lei Yang; Wei-Wei Shen; Quan-Song Zhu; Chun-Yu Lai; An-Cheng Luo; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Spatial distribution and dynamics of carbon storage in natural Larix gmelinii forest in Daxing’anling mountains of Inner Mongolia, northeastern China - Sheng-wang Meng; Qi-jing Liu; Quan-quan Jia; Hui-xia Zhuang; Ying Qi; Cheng-xue Lu; Liu-bao Deng (Journal of Mountain Science, 2017)

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

Mapping QTLs controlling kernel dimensions in a wheat inter-varietal RIL mapping population - Ruiru Cheng; Zhongxin Kong; Liwei Zhang; Quan Xie; Haiyan Jia; Dong Yu; Yulong Huang; Zhengqiang Ma (Theoretical and Applied Genetics, 2017)

A Fluorescence Sensor for Lead (II) Ions Determination Based on Label-Free Gold Nanoparticles (GNPs)-DNAzyme Using Time-Gated Mode in Aqueous Solution - Xiao-Yu Wang; Cheng-Gang Niu; Li-Juan Guo; Liu-Yin Hu; Sheng-Quan Wu; Guang-Ming Zeng; Fei Li (Journal of Fluorescence, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Molecular characterisation and functional analysis of a cytochrome P450 gene in cotton - Kexue Zhou; Lu Long; Quan Sun; Weina Wang; Wei Gao; Zongyan Chu; Chaowei Cai; Jianchuan Mo; Jieru Cheng; Xiangrui Zhang; Yujia Liu; Xiongming Du; et al. (Biologia, 2017)

Chemical forms of heavy metals in agricultural soils affected by coal mining in the Linhuan subsidence of Huaibei Coalfield, Anhui Province, China - Wenqin Shang; Quan Tang; Liugen Zheng; Hua Cheng (Environmental Science and Pollution Research, 2016)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

Citricoccus lacusdiani sp. nov., an actinobacterium promoting Microcystis growth with limited soluble phosphorus - Bing-Huo Zhang; Nimaichand Salam; Juan Cheng; Min Xiao; Han-Quan Li; Jian-Yuan Yang; Dai-Ming Zha; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

Camellia nanningensis sp. nov.: the earliest fossil wood record of the genus Camellia (Theaceae) from East Asia - Lu-Liang Huang; Jian-Hua Jin; Cheng Quan; Alexei A. Oskolski (Journal of Plant Research, 2016)

Progression and inflammation of human myeloid leukemia induced by ambient PM2.5 exposure - Xiao-Ting Jin; Mei-Lan Chen; Rui-Jin Li; Quan An; Li Song; Yi Zhao; Hong Xiao; Long Cheng; Zhuo-Yu Li (Archives of Toxicology, 2016)

Characterization of the relationship between vascular bundles features and indica-allelic frequency using a seventh filial generations of indica × japonica rice crosses - Tiansheng Liu; Wenjing Bi; Jia Zhang; Yue Cui; Zhiqiang Yan; Yuanzheng Wang; Cheng Fei; Hai Xu; Liang Tang; Wenfu Chen; Jian Sun; Quan Xu (Euphytica, 2016)

Effect of contact state on the shear behavior of artificial rock joint - Zhi Cheng Tang; Run Qiu Huang; Quan Sheng Liu; Louis Ngai Yuen Wong (Bulletin of Engineering Geology and the Environment, 2016)

Analysis of EDZ Development of Columnar Jointed Rock Mass in the Baihetan Diversion Tunnel - Xian-Jie Hao; Xia-Ting Feng; Cheng-Xiang Yang; Quan Jiang; Shao-Jun Li (Rock Mechanics and Rock Engineering, 2016)

First Oligocene mummified plant Lagerstätte at the low latitudes of East Asia - Cheng Quan; QiongYao Fu; GongLe Shi; YuSheng Liu; Long Li; XiaoYan Liu; JianHua Jin (Science China Earth Sciences, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

Phylogenetic analysis of Festuca–Lolium complex using SRAP markers - Yajuan Cheng; Xiao Ma; Kai Zhou; Mike W. Humphreys; Xin Quan Zhang (Genetic Resources and Crop Evolution, 2016)

Characterization and expression analysis of the expansin gene NnEXPA1 in lotus Nelumbo nucifera - Neng Cheng; Xiao-Fei Zeng; Xing-Fei Zheng; Ying Diao; You-Wei Wang; Ke-Qiang Xie; Ming-Quan Zhou; Zhong-Li Hu (Biologia, 2016)

Regulation of HepG2 cell apoptosis by hepatitis C virus (HCV) core protein via the sirt1–p53–bax pathway - Shenghu Feng; Min Li; Jinqian Zhang; Shunai Liu; Qi Wang; Min Quan; Mengran Zhang; Jun Cheng (Virus Genes, 2015)

Short-Term Effects and Safety Analysis of Retrograde Autologous Blood Priming for Cardiopulmonary Bypass in Patients with Cardiac Valve Replacement Surgery - Ming Cheng; Jun-Quan Li; Tian-Chi Wu; Wei-Chen Tian (Cell Biochemistry and Biophysics, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Mid-Miocene (~17 Ma) quartz diorite porphyry in Ciemas, West Java, Indonesia, and its geological significance - Cheng-Quan Wu; Zheng-Wei Zhang; Chao-Fei Zheng; Jun-Hua Yao (International Geology Review, 2015)

Distribution and health risk assessment of mercury in urban street dust from coal energy dominant Huainan City, China - Liugen Zheng; Quan Tang; Jiamin Fan; Xiaoyu Huang; Chunlu Jiang; Hua Cheng (Environmental Science and Pollution Research, 2015)

Synthesis and biological evaluation of novel 1,2-benzisothiazol-3-one-derived 1,2,3-triazoles as caspase-3 inhibitors - Zhenfei Guo; Zhihui Yan; Xiaowei Zhou; Quan Wang; Meiqi Lu; Wei Liu; Honggang Zhou; Cheng Yang; Edward J. McClain (Medicinal Chemistry Research, 2015)

Enrichment of cardiac differentiation by a large starting number of embryonic stem cells in embryoid bodies is mediated by the Wnt11-JNK pathway - Ming Chen; Cheng Qian; Lin-Lin Bi; Fang Zhao; Guang-Yu Zhang; Zhi-Quan Wang; Xue-Dong Gan; Yang-Gan Wang (Biotechnology Letters, 2015)

Cloning and characterization of the genes encoding the small and large subunit of the ADP-glucose pyrophosphorylase in lotus (Nelumbo nucifera Gaertn) - Neng Cheng; Xiao-Fei Zeng; Xing-Fei Zheng; Ying Diao; You-Wei Wang; Ke-Qiang Xie; Ming-Quan Zhou; Zhong-Li Hu (Acta Physiologiae Plantarum, 2015)

Mechanical Model for Predicting Closure Behavior of Rock Joints Under Normal Stress - Zhi-Cheng Tang; Quan-Sheng Liu; Cai-Chu Xia; Ying-Long Song; Ji-Hui Huang; Chun-Bo Wang (Rock Mechanics and Rock Engineering, 2014)

Combined effects of the BDNF rs6265 (Val66Met) polymorphism and environment risk factors on psoriasis vulgaris - Cheng Quan; Kun-Ju Zhu; Chi Zhang; Zhong Liu; Huan Liu; Cheng-Yao Zhu; Ke-Shen Li; Yi-Ming Fan; Jie Zheng (Molecular Biology Reports, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Typhoon-enhanced upwelling and its influence on fishing activities in the southern East China Sea - Yi Chang; Jui-Wen Chan; Yuan-Chao Angelo Huang; Wei-Quan Lin; Ming-An Lee; Kuo-Tien Lee; Cheng-Hsin Liao; Kae-Yih Wang; Yi-Chun Kuo (International Journal of Remote Sensing, 2014)

The transcriptional response of apple alcohol acyltransferase (MdAAT2) to salicylic acid and ethylene is mediated through two apple MYB TFs in transgenic tobacco - Peng-Cheng Li; Shao-Wei Yu; Jin Shen; Qing-Qing Li; Da-Peng Li; De-Quan Li; Cheng-Chao Zheng; Huai-Rui Shu (Plant Molecular Biology, 2014)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

The activation of TLR7 regulates the expression of VEGF, TIMP1, MMP2, IL-6, and IL-15 in Hela cells - Lei Li; Feng-Wei Cheng; Fang Wang; Bo Jia; Xin Luo; Sheng-Quan Zhang (Molecular and Cellular Biochemistry, 2014)

Streptomyces jiujiangensis sp. nov., isolated from soil in South China - Bing-Huo Zhang; Juan Cheng; Li Li; Yong-Guang Zhang; Hong-Fei Wang; Han-Quan Li; Jian-Yuan Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Gardiquimod inhibits the expression of calcium-induced differentiation markers in HaCaT cells - Bo Jia; Xin Luo; Feng-Wei Cheng; Lei Li; Dao-Jun Hu; Fang Wang; Sheng-Quan Zhang (Molecular Biology Reports, 2013)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Auto-registration and orthorecification algorithm for the time series HJ-1A/B CCD images - Jin-hu Bian; Ai-nong Li; Hua-an Jin; Guang-bin Lei; Cheng-quan Huang; Meng-xue Li (Journal of Mountain Science, 2013)

Validation of global land surface satellite (GLASS) downward shortwave radiation product in the rugged surface - Hua-an Jin; Ai-nong Li; Jin-hu Bian; Zheng-jian Zhang; Cheng-quan Huang; Meng-xue Li (Journal of Mountain Science, 2013)

Association of IL-1 Receptor Antagonist Gene VNTR Polymorphism with Ischemic Stroke in the Chinese Uyghur Population - Yeqing Tong; Jinjun Han; Xuhua Guan; Zuxun Lu; Xiaoping Miao; Jianjun Ye; Shuang-yi Hou; Yanwei Zhang; Yijie Geng; Yang Li; Faxian Zhan; Jiafa Liu; et al. (Biochemical Genetics, 2013)

Matrine suppresses expression of adhesion molecules and chemokines as a mechanism underlying its therapeutic effect in CNS autoimmunity - Quan-Cheng Kan; Lin Zhu; Nan Liu; Guang-Xian Zhang (Immunologic Research, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Regulatory long non-coding RNA and its functions - Yong Huang; Ning Liu; Jian Ping Wang; Yu Qin Wang; Xue Li Yu; Zhan Bin Wang; Xiang Chao Cheng; Quan Zou (Journal of Physiology and Biochemistry, 2012)

Hydrogen peroxide functions as a secondary messenger for brassinosteroids-induced CO2 assimilation and carbohydrate metabolism in Cucumis sativus - Yu-ping Jiang; Fei Cheng; Yan-hong Zhou; Xiao-jian Xia; Wei-hua Mao; Kai Shi; Zhi-xiang Chen; Jing-quan Yu (Journal of Zhejiang University-SCIENCE B, 2012)

3D-QSAR and molecular docking studies of hydroxamic acids as peptide deformylase inhibitors - Jian Gao; Yuanhua Cheng; Wei Cui; Quan Chen; Fushi Zhang; Yuguo Du; Mingjuan Ji (Medicinal Chemistry Research, 2012)

Zygote-derived seedling production of Sargassum thunbergii: focus on two frequently experienced constraints in tank culture of seaweed - Quan Sheng Zhang; Yong Zheng Tang; Shi Kai Liu; Shu Bao Zhang; Zhi Cheng Lu; Shao Hua Cu; Yong Qiang Yu (Journal of Applied Phycology, 2012)

Synthesis, structure, and biological activity of novel (oxdi/tri)azoles derivatives containing 1,2,3-thiadiazole or methyl moiety - Xing-Hai Liu; Li Pan; Jian-Quan Weng; Cheng-Xia Tan; Yong-Hong Li; Bao-Lei Wang; Zheng-Ming Li (Molecular Diversity, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Decontamination of Bacillus subtilis var. niger spores on selected surfaces by chlorine dioxide gas - Yan-ju Li; Neng Zhu; Hai-quan Jia; Jin-hui Wu; Ying Yi; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2012)

DNA Methylation in Genomes of Several Annual Herbaceous and Woody Perennial Plants of Varying Ploidy as Detected by MSAP - Ai Li; Bao-Quan Hu; Zhen-Yi Xue; Li Chen; Wei-Xing Wang; Wen-Qin Song; Cheng-Bin Chen; Chun-Guo Wang (Plant Molecular Biology Reporter, 2011)

Synthesis and antidepressant-like action of N-(2-hydroxyethyl) cinnamamide derivatives in mice - Xian-Qing Deng; Di Wu; Cheng-Xi Wei; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

Microsatellite Analysis of Homozygosity Progression of Heterozygous Genotypes Segregating in the Rice Subspecies Cross Pei’ai64s/Nipponbare - Yong-shu Liang; Qi-jun Zhang; Shi-quan Wang; Li-yong Cao; Zhi-qiang Gao; Ping Li; Shi-hua Cheng (Biochemical Genetics, 2011)

Trend of Santonian (Late Cretaceous) atmospheric CO2 and global mean land surface temperature: Evidence from plant fossils - ChuanBiao Wan; DeHai Wang; ZhanPing Zhu; Cheng Quan (Science China Earth Sciences, 2011)

Synthesis and evaluation of 7-substituted-3,4-dihydrobenzo[f][1,4]oxazepin-5(2H)-ones as anticonvulsant and hypnotic agents - Xian-Qing Deng; Ming-Xia Song; Cheng-Xi Wei; Zhi-Gang Sun; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

Population dynamics, phenology, and overwintering of Bactrocera dorsalis (Diptera: Tephritidae) in Hubei Province, China - Peng Han; Xu Wang; Chang-Ying Niu; Yong-Cheng Dong; Jing-Quan Zhu; Nicolas Desneux (Journal of Pest Science, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Isolation and Functional Characterization of ZmDBP2 Encoding a Dehydration-Responsive Element-Binding Protein in Zea mays - Chang-Tao Wang; Quan Yang; Cheng-Tao Wang (Plant Molecular Biology Reporter, 2011)

RETRACTED ARTICLE: SOCS3 inhibits insulin signaling in porcine primary adipocytes - Shuang-Juan Yang; Cheng-Quan Xu; Jiang-Wei Wu; Gong-She Yang (Molecular and Cellular Biochemistry, 2010)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Synthesis of 6-(3-substituted-4H-1,2,4-triazol-4-yl)-2-phenylbenzo[d]oxazoles as potential anticonvulsant agents - Cheng-Xi Wei; Di Wu; Zhi-Gang Sun; Kyu-Yun Chai; Zhe-Shan Quan (Medicinal Chemistry Research, 2010)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

IGF-1 and BMP-2 Induces Differentiation of Adipose-Derived Mesenchymal Stem Cells into Chondrocytes-Like Cells - Chunhou An; Yang Cheng; Quan Yuan; Jianjun Li (Annals of Biomedical Engineering, 2010)

Development and identification of a wheat-Psathyrostachys huashanica addition line carrying HMW-GS, LMW-GS and gliadin genes - Ji-Xin Zhao; Wan-Quan Ji; Jun Wu; Xin-Hong Chen; Xue-Ni Cheng; Jian-Wei Wang; Yu-Hui Pang; Shu-Hui Liu; Qun-Hui Yang (Genetic Resources and Crop Evolution, 2010)

Analysis of genome expression in the response of Oryza granulata to Xanthomonas oryzae pv oryzae - Yu Luo; Guang-Lei Lv; Wen-Ting Wu; Shan-Na Chen; Zai-Quan Cheng (Molecular Biology Reports, 2010)

Cytocompatibility of regenerated silk fibroin film: a medical biomaterial applicable to wound healing - Tie-lian Liu; Jing-cheng Miao; Wei-hua Sheng; Yu-feng Xie; Quan Huang; Yun-bo Shan; Ji-cheng Yang (Journal of Zhejiang University-SCIENCE B, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Establishment and characterization of a new highly metastatic human osteosarcoma cell line - Yuxi Su; Xiaoji Luo; Bai-Cheng He; Yi Wang; Liang Chen; Guo-Wei Zuo; Bo Liu; Yang Bi; Jiayi Huang; Gao-Hui Zhu; Yun He; Quan Kang; et al. (Clinical & Experimental Metastasis, 2009)

Fabrication of a Novel Core-Shell Gene Delivery System Based on a Brush-Like Polycation of α, β–Poly (L-Aspartate-Graft-PEI) - Jia-Hui Yu; Ji-Shan Quan; Jung-Taek Kwon; Cheng-Xiong Xu; Bo Sun; Hu-Lin Jiang; Jae-Woon Nah; Eun-Mi Kim; Hwan-Jeong Jeong; Myung-Haing Cho; Chong-Su Cho (Pharmaceutical Research, 2009)

Origin of the Gangdise (Transhimalaya) Permian arc in southern Tibet: Stratigraphic and volcanic geochemical constraints - Quan‐Ru Geng; Zhi‐Ming Sun; Gui‐Tang Pan; Di‐Cheng Zhu; Li‐Quan Wang (Island Arc, 2009)
The well‐studied Mesozoic and Cenozoic volcanic rocks of the Gangdise Terrane, southern Tibet, are widely interpreted to have resulted from subduction of the Neotethys; however, Late Paleozoic volcanic rocks and their tectonic setting remain poorly studied. Based on new geological data, we carried out stratigraphical and geochemical analyses of Permian volcano‐stratigraphic sequences within an east–west‐trending, fault‐bounded zone of uplift in the central Gangdise Terrane. Sedimentary rocks in this area consist of platform carbonates and terrigenous clastic rocks that represent widespread shallow‐marine sedimentary basins developed around northern Gondwana. A regression or tectonic uplift event is recorded in Permian sedimentary rocks that show the local development of fluvial environments. The sedimentary succession contains evidence of two volcanic stages: a period of basaltic extrusions and younger explosive felsic magmatism. The first volcanic stage is Early and Middle Permian in age. Tholeiitic basaltic lavas are exposed around Maizhokunggar (Tangjia) and Lhunzhub in central Gangdise. The Lower Permian basalts are relatively enriched in MgO (4.58–12.19%), whereas the Middle Permian basalts are characterized by high Al 2 O 3 contents (11.75–21.22%). Rocks of both ages are enriched in large‐ion lithophile elements (LILE) and light rare earth elements (LREE), and show pronounced negative Nb and Ta anomalies. Total REE contents and light (LREE)/heavy (HREE) ratios increased from the Early to Middle Permian. Observed variations in initial Sr, Nd, and Pb isotopes ( 87 Sr/ 86 Sr i = 0.7013–0.7066, 207 Pb/ 204 Pb i = 15.53–15.63, and 208 Pb/ 204 Pb i = 38.04–38.64 for a given 206 Pb/ 204 Pb i ; εNd = +0.69 to −11.55) can be explained by crustal interaction with mantle sources, as is characteristic of metasomatism by slab‐derived fluids or assimilation and fractional crystallization (AFC) processes during magmatic evolution. The observed geochemical signatures, coupled with stratigraphic constraints, support the hypothesis that an initial arc formed during the Permian due to southward subduction of the Paleotethys, predating the well‐known Mesozoic arc preserved in the Gangdise Terrane.

Improvement of chloroperoxidase stability by covalent immobilization on chitosan membranes - Li-Hua Zhang; Chao-Hong Bai; Ying-Song Wang; Yu-Cheng Jiang; Man-Cheng Hu; Shu-Ni Li; Quan-Guo Zhai (Biotechnology Letters, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Enhanced Tonoplast H+-ATPase Activity and Superoxide Dismutase Activity in the Halophyte Suaeda salsa Containing High Level of Betacyanin - Chang-Quan Wang; Cheng Xu; Ji-Guo Wei; Hong-Bo Wang; Shao-Hai Wang (Journal of Plant Growth Regulation, 2008)

Establishment and characterization of two embryonic cell lines of Bombyx mori - Min-Hui Pan; Shi-Quan Xiao; Min Chen; Xi-Jun Hong; Cheng Lu (In Vitro Cellular & Developmental Biology - Animal, 2007)

Characterization of E. coli O24 and O56 O Antigen Gene Clusters Reveals a Complex Evolutionary History of the O24 Gene Cluster - Jiansong Cheng; Quan Wang; Wei Wang; Ying Wang; Lei Wang; Lu Feng (Current Microbiology, 2006)

Variants of Green Fluorescent Protein GFPxm - Wen-Xin Luo; Tong Cheng; Bao-Quan Guan; Shao-Wei Li; Ji Miao; Jun Zhang; Ning-Shao Xia (Marine Biotechnology, 2006)

Variants of Green Fluorescent Protein GFPxm - Wen-Xin Luo; Tong Cheng; Bao-Quan Guan; Shao-Wei Li; Ji Miao; Jun Zhang; Ning-Shao Xia (Marine Biotechnology, 2006)

Role of nitrate in biological phosphorus removal in a sequencing batch reactor - Hua Zou; Guo-Cheng Du; Wen-Quan Ruan; Jian Chen (World Journal of Microbiology and Biotechnology, 2006)

Codon-modifications and an endoplasmic reticulum-targeting sequence additively enhance expression of an Aspergillus phytase gene in transgenic canola - Ri-He Peng; Quan-Hong Yao; Ai-Sheng Xiong; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2006)

Safety analysis of water resources and eco-environment in Shiyang River Basin - Ji-shi Zhang; Yong-qiu Zhang; Rui-feng Pu; Ren-sheng Chen; Zhong-shan Cheng; Ming-quan Wang (Chinese Geographical Science, 2005)

Functional promoter polymorphism in the TBX21 gene associated with aspirin-induced asthma - Mitsuteru Akahoshi; Kazuhiko Obara; Tomomitsu Hirota; Akira Matsuda; Koichi Hasegawa; Naomi Takahashi; Makiko Shimizu; Kazuko Nakashima; Lei Cheng; Satoru Doi; Hiroshi Fujiwara; Akihiko Miyatake; et al. (Human Genetics, 2005)

Vitreoscilla hemoglobin overexpression increases submergence tolerance in cabbage - Xian Li; Ri-He Peng; Hui-Qin Fan; Ai-Sheng Xiong; Quan-Hong Yao; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

Seasonal variations of riverine organic carbon contents in Makou and Hekou gauge stations of the Zhujiang River, China - Quan-zhou Gao; Cheng-de Shen; Yan-min Sun; Wei-xi Yi; Jia-mo Fu; Guo-ying Sheng (Chinese Geographical Science, 2000)